Environmentally sustainable extraction and recovery of rare earth elements from alkali-activated carbonatite using dual water and acid leaching and clay adsorption - Ali H. Almohammed; Uttam K. Bhui; Dwijesh Ray; Anil D. Shukla; N. Madhavan (Minerals Engineering, 2026)

Comparative genomics analysis of aneuploidy and cellular fragmentation dynamics in mammalian embryos - R. Tippner-Hedges; J. Budrewicz; E.S. Rubin; K. Ray; B.A. Davis; M. Okovat; L. Carbone; E.S. Metcalf; S.L. Chavez (Journal of Equine Veterinary Science, 2026)

Regional bio‐mobility of bovines during the Harappan period: Evidence from stable C–O–Sr isotopes of faunal bioapatite at Kanmer and Tigrana - Milan K. Mahala; Amzad H. Laskar; Pankaj Goyal; Jeewan S. Kharakwal; Narender Parmar; Yadubir S. Rawat; Angad Lamba; Alok K. Kanungo; Jyotiranjan S. Ray (Journal of Quaternary Science, 2026)
Studies on biomobility in the Indus Valley Civilisation (IVC) or the Harappan Culture provide important insights into pastoral practices, trade and environmental adaptation that shaped the civilisation's economy and social networks. At its height, the IVC engaged in extensive trade across its vast territory, resulting in cultural and economic change across diverse ecological zones. Although archaeological finds indicate trade in artefacts throughout the civilisation, our understanding of human and animal mobility remains limited due to a lack of geochemical and isotopic data on provenance. A key unresolved issue in biomobility is distinguishing between local and broader animal husbandry practices and their trade connections. To address this, we analysed faunal teeth, bone bioapatite and bone‐encased soil using C–O–Sr–Nd isotopes from two Harappan sites, Kanmer (Gujarat) and Tigrana (Haryana), located more than 900 km apart. Our isotope data and the existing literature suggest that, in Kanmer, specialised animal‐feeding methods were used, and local rainfall was the primary water source across all settlements. Data from both sites show that most sheep/goat were raised locally with little movement; however, bovines in Kanmer from the mature and late‐mature phases had diverse, possibly non‐local origins, likely from Haryana. At Tigrana, some animals also showed signs of movement from nearby regions. Regional movement of bovines from a better watered region to a semi‐arid region may indicate trading as an important aspect of this civilisation embedded within broader social and economic networks.

Multistage sedimentary-metamorphic-hydrothermal evolution of the Shivrajpur manganese deposits, Champaner Group, Aravalli Supergroup, western India - Ali H. Almohammed; Uttam K. Bhui; Dwijesh Ray; N. Madhavan (Geosciences Journal, 2026)

Characterizing rock-mass hillslopes in Ladakh Himalaya; implications for sustainable development - Imlirenla Jamir; Nithya D. Suresh; K. J.P. Lakshmi; Labani Ray; Vipin Kumar (Environment, Development and Sustainability, 2026)

Comprehensive analysis of gene expression profiles revealed increased expression of genes related to proteasome in feline nasal lymphoma - Takumi Tsuruta; Hirotaka Tomiyasu; Hiroki Sakuma; Shotaro Shimano; Itsuma Nagao; Hiroto Toyoda; Ray Fukuoka; Aki Ohmi; Naoki Fujita; Yasuyuki Momoi; Takafumi Ohshima; Aki Fujiwara-Igarashi; et al. (Research in Veterinary Science, 2026)

Uncertainty Quantification in Climate Forecasting: How Bayesian Structural Time Series Models Excel Over Traditional and Data-Driven Techniques - Achal Lama; Soumik Ray; Pradip Kumar Sahu; K. N. Singh; Bishal Gurung; Bikramjeet Ghose; Pradeep Mishra; Tufleuddin Biswas (Water Resources Management, 2026)

Developing a clay-assisted method for REE recovery from Amba Dongar carbonatite - Ali H. Almohammed; Uttam K. Bhui; Dwijesh Ray; N. Madhavan (Acta Geochimica, 2026)

Giant voltage generation in robust, self-healing elastomeric nanocomposites for effluents energy harvesting, sensing, and electromagnetic radiation shielding - Shovan Biswas; Sayan Chakraborty; Jasomati Nayak; Palash Das; Ankur Katheria; Chinmayee Mandar Mhaskar; Ayan Roy Chaudhuri; Samit K. Ray; Narayan Ch. Das (Chemical Engineering Journal, 2026)

Impact of urbanization and global warming on sea-breeze, heat stress and cooling demand over greater Houston area - Mukul Tewari; Francisco Salamanca; Aditya K. Dubey; Pallav Ray; Lloyd A. Treinish; Jorge E. Gonzalez-Cruz; Vinnarasi Rajendran (Atmospheric Research, 2026)

Is cinchona (Cinchona sp.) a sustainable land use practice in the Eastern Himalayas of India? A comparative study with other land uses in relation to soil properties and carbon indices - S. K. Reza; Ruma Das; K. M. Hati; S. Chattaraj; A. Daripa; Sreyasi Talukdar; F. H. Rahman; S. K. Ray (Environmental Sustainability, 2026)

Correction: Statistical investigation of heatwave trends and change points in Telangana, India - Kona Naga Venkata Lakshmi Laasya; Supriya Kallakuri; Santosha Rathod; Lakshmi Neelima; Debasish Chakraborty; S. Vishnu Shankar; Mrinmoy Ray; Nobin Chandra Paul; Shahid Saleem; Ammaladinne Tharun Kumar; Nirmala Bandumula; Kirttiranjan Baral; et al. (Natural Hazards, 2026)

Traditional cupping-inspired sampling of skin interstitial fluid combined with gold nanobipyramids for multicolor visual detection of miRNAs - Qing Xiong; Chuxiang Hu; Siqi Li; Lisong Pang; Benson K. Kosgei; Xiaoyu Deng; Zhixin Li; Ray P.S. Han; Yingzhou Tao; Shaohua Xu (Chemical Engineering Journal, 2026)

Natural silk fibroin – MOF nanocomposite based wearable triboelectric nanogenerators for energy harvesting and real-time IoT-enabled healthcare monitoring - Sayan Chakraborty; Samit K. Ray (Chemical Engineering Journal, 2026)

Biotransformation of lactose-free acid whey by Chlorella vulgaris and Tetradesmus obliquus into value-added products - Duygu Ozcelik; Rocio Espinosa; Radhakrishna Shetty; Shyam Suwal; Henriette Lyng Røder; Charlotte Jacobsen; Colin Ray; Brijesh K. Tiwari; Poul Erik Jensen; Mahesha M. Poojary (Bioresource Technology, 2026)

Statistical investigation of heatwave trends and change points in Telangana, India - Kona Naga Venkata Lakshmi Laasya; Supriya Kallakuri; Santosha Rathod; Lakshmi Neelima; Debasish Chakraborty; S. Vishnu Shankar; Mrinmoy Ray; Nobin Chandra Paul; Shahid Saleem; Ammaladinne Tharun Kumar; Nirmala Bandumula; Kirttiranjan Baral; et al. (Natural Hazards, 2026)

Age and geochemistry of carbonatites and associated silicate rocks in Sarnu-Dandali alkaline complex, Deccan Large Igneous Province: Evidence for melt immiscibility and plume-lithosphere interaction - Milan K. Mahala; Jyotiranjan S. Ray; Kanchan Pande (Contributions to Mineralogy and Petrology, 2026)

Complex Love Numbers in the Diurnal and Semidiurnal Tidal Bands Determined from Satellite Tracking and Altimetry - R. D. Ray; B. D. Loomis; K. E. Rachlin; J. J. Otero Torres (Pure and Applied Geophysics, 2026)

Mangroves uptake lithium and beryllium, contributing to the mitigation of contamination risks in the sundarbans - Sanjay Kumar Mandal; Raghab Ray; Buddhadeb Dutta; Tapan K Jana (Ecotoxicology, 2026)

Tracking norovirus diversity at a global scale through wastewater metagenomics - Ray W. Izquierdo-Lara; Nathalie Worp; Mark Olthof; Bas B. Oude Munnink; Claudia M.E. Schapendonk; Divyae K. Prasad; Frank M. Aarestrup; Marion P.G. Koopmans; Miranda de Graaf (Water Research, 2025)

Systematic evaluation of Tox21 compounds that target β-adrenergic receptors and their role in cardiotoxicity - Xi Luo; Li Zhang; Srilatha Sakamuru; Precious A. Adesina; Jinghua Zhao; Menghang Xia; Tuan Xu; Deborah K. Ngan; Jameson Travers; Savannah Wood; Ray Sukhawanit; Anthony Garrison; et al. (Toxicology and Applied Pharmacology, 2025)

Simultaneous removal of Hg(II), Pb(II), Ni(II), Cd(II), Cu(II), Mn(II), Fe(II), ions and fluoride from groundwater by Fluoride Nilogon: Phosphoric acid-crushed limestone treatment (PACLT) - Tushmita Das; Saranga Baishya; Shamiran Baroi; Priya Devi; Priyanka Ray; Rituparna Saikia; Robin K. Dutta (Journal of Water Process Engineering, 2025)

Environmental life cycle assessment of surgical versus conservative care pathways for an anterior cruciate ligament injury - Polina Boiko; Anne-Violette Bruyneel; Nicolas Ray; Philippe M. Tscholl; Martin K. Patel (Journal of Cleaner Production, 2025)

NCBI Orthologs: Public Resource and Scalable Method for Computing High-Precision Orthologs Across Eukaryotic Genomes - Dong-Ha Oh; Alexander Astashyn; Barbara Robbertse; Nuala A. O’leary; W. Ray Anderson; Laurie Breen; Eric Cox; Olga Ermolaeva; Robert Falk; Vichet Hem; J. Bradley Holmes; Patrick Masterson; et al. (Journal of Molecular Evolution, 2025)
Orthologs are fundamental for enabling comparative genomics analyses that further our understanding of eukaryotic biology. The unprecedented increase in the availability of high-quality eukaryotic genomes necessitates scalable and accurate methods for orthology inference. The National Center for Biotechnology Information (NCBI) developed “NCBI Orthologs”, a resource and a computational pipeline designed to meet this challenge within the NCBI RefSeq framework. This system integrates protein similarity, nucleotide alignment, and microsynteny to achieve high-precision ortholog assignments across diverse eukaryotes. The pipeline leverages high-quality RefSeq annotations and processes genomes individually, ensuring scalability. Resulting ortholog data, organized into gene-level anchored sets, enables propagation of functional annotation information and facilitates comparative genomics. Critically, these data are integrated into the NCBI Gene resource, providing users with access from various entry points. The NCBI Datasets resource provides an intuitive interface to explore orthologous relationships on the web and allows bulk data download via the web, command-line tools, and an API. We detail the methodology, including anchor species selection and the decision tree used to arrive at high-confidence one-to-one orthology relationships. NCBI Orthologs is a valuable resource for facilitating functional annotation efforts and enhancing our understanding of eukaryotic gene evolution.

Comparison of clinical, radiological and outcome parameters in patients with progressive multifocal leukoencephalopathy (PML) with and without HIV infection: a cohort study - Farsana Mustafa; Anuj Ajayababu; Ajay Garg; Megha Brijwal; Divyani Garg; Manish Soneja; Aashish Choudhary; Lalit Dar; Shariq A. Shah; Venugopalan Y Vishnu; Animesh Ray; Neeraj Nischal; et al. (Journal of NeuroVirology, 2025)

Domestication Reduces Floral Volatile Richness in Squash (Cucurbitaceae: Cucurbita) But Conserves Key Compounds Critical for Pollinator Attraction - Avehi Singh; Swayamjit Ray; Kristen K. Brochu-DeLuca; Andrew J. Myrick; Nathaniel B. McCartney; Jared G. Ali; Margarita M. López-Uribe (Journal of Chemical Ecology, 2025)
The domestication of crops leads to profound changes on plant phenotypes, yet its effects on floral traits mediating plant-pollinator interactions remain poorly understood. Floral volatile organic compounds (VOCs) play a crucial role in pollinator attraction by signaling the presence and quality of available floral resources. Here, we characterize VOC composition in Cucurbita , a genus containing multiple wild and domesticated species, to investigate how domestication affects floral volatiles. Then, we combined electrophysiology, blue vane trap field assays and pollinator visitation experiments to assess how the squash specialist pollinator, Xenoglossa pruinosa , responded to existing VOCs across different wild and domesticated plant species. Our results reveal significant compound losses within domesticated species blends. Combined gas chromatography-electroantennography (GC-EAG) identified ten electrophysiologically active compounds across wild and domesticated squash VOCs. Field assays assessing bee attraction to individual antennally active compounds using modified blue vane traps with compound lures identified 1,4-dimethoxybenzene (a dominant volatile in domesticated squash blends) as an attractant for bees in isolation. We also found significant associations between bee visitation (assessed as floral approaches and nectaring behaviors) and increased emissions of 1,4-dimethoxybenzene, dihydro-β-ionone, and ( E )-nerolidol as well as reduced emissions of linalool and methyl salicylate. Our findings provide novel insights into the chemical ecology of crop-pollinator interactions, demonstrating that domestication can reshape plant-pollinator communication mechanisms.

The teat skin microbiota of organic primiparous dairy cows is dynamic during the transition period - C.J. Dean; T. Ray; F. Peña-Mosca; T.J. Wehri; K. Sharpe; A.M. Antunes; E. Doster; L. Fernandes; V.F. Calles; C. Bauman; B. Heins; P. Pinedo; et al. (Preventive Veterinary Medicine, 2025)

Deciphering cGAS-STING signaling: implications for tumor immunity and hepatocellular carcinoma - Harish C. Chandramoorthy; Raed Obaid Saleh; Farag M. A. Altalbawy; Jaafaru Sani Mohammed; Subbulakshmi Ganesan; Mayank Kundlas; J Premkumar; Subhashree Ray; Yasser Fakri Mustafa; Jamal K. Abbas (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Seaweed extract-based biostimulants alleviate nutrient stress and enhance productivity and grain quality of wheat through efficient use of fertilizers nutrients under sub-optimal NPK application - Bijan Kumar Mondal; Abir Dey; M. C. Meena; Debarup Das; Archana Singh; Shivani Nagar; Prasenjit Ray; P. K. Upadhyay; Deepak Bamel; Amit Kumar Dash; Krishna Kumar Mourya; Narender Yadava; et al. (Journal of Applied Phycology, 2025)

Complete mitochondrial DNA genome of the Indian Chhattisgarh duck and its phylogenetic analysis - Rajni Kumari; Ratna Prabha; Tirupati Rao Golla; P. K. Ray; Reena Kamal; Jaipal S. Choudhary; Abhay Kumar; Sanjay Kumar; Shanker Dayal; P. C. Chandran; Jyoti Kumar; M. K. Tripathi; et al. (Journal of Genetics, 2025)

Modelling Price Dynamics in Indian Potato Markets: A Comprehensive Econometric Approach - Rajeev Ranjan Kumar; S. Vishnu Shankar; Ronit Jaiswal; Jaiprakash Bisen; Kapil Choudhary; V. Lavanya; Mrinmoy Ray; K. N. Singh (Potato Research, 2025)

In silico exploration of pyrocannabinoid interactions with key protein targets - Giovanni A. Ramirez; Tesfay T. Tesfatsion; Monica K. Pittiglio; Kyle P. Ray; Andrew Westerkamp; Westley Cruces (In Silico Pharmacology, 2025)

A framework for sustainable urban settlement planning: Integrating geographic information system and multi-criteria decision analysis - S. K. Ray; A. Teja; S. Chaudhary; M. H. Kumar; R. Rahul; K. Rammohan; D. Himabindu (Environment, Development and Sustainability, 2025)

Geochronology of the Vindhyan Supergroup: Implications for the closure of the Proterozoic basins of India - Bivin G. George; Jyotiranjan S. Ray; Milan K. Mahala; J. Amal Dev; J.K. Tomson; J. Haripriya; Alok Kumar (Precambrian Research, 2025)

A2B adenosine receptor-triggered intracellular calcium mobilization: Cell type-dependent involvement of Gi, Gq, Gs proteins and protein kinase C - Zhan-Guo Gao; Ray R. Gao; Clayton K. Meyer; Kenneth A. Jacobson (Purinergic Signalling, 2025)
Activation of PLCβ enzymes by G iβγ and G αq/11 proteins is a common mechanism to trigger cytosolic Ca 2+ increase. We and others reported that G αq/11 inhibitor FR900359 (FR) can inhibit both G αq - and, surprisingly, G iβγ -mediated intracellular Ca 2+ mobilization. Thus, the G αi -G βγ -PLCβ-Ca 2+ signaling axis depends entirely on the presence of active G αq , which reasonably explained FR-inhibited G iβγ -induced Ca 2+ release. However, the conclusion that G iβγ signaling is controlled by G αq derives mostly from HEK293 cells. Here we show that indeed in HEK293 cells both G αq/11 siRNA and G αq/11 inhibitors diminished Ca 2+ increase triggered by native G q -coupled P2Y 1 receptors, or by transfected G i -coupled A 1 - or G s -coupled A 2B adenosine receptors (ARs). However, in T24 bladder cancer cells, G i inhibitor PTX, but not G αq/11 inhibitors, FR, YM254890 (YM) or G q/11 siRNA, inhibited Ca 2+ increase triggered by native A 2B AR activation. Simultaneous inactivation of G i and G s further suppressed A 2B AR-triggered Ca 2+ increase in T24 cells. The G αq/11 inhibitor YM fully and partially inhibited endogenous P2Y 1 - and β 2 -adrenergic receptor-induced Ca 2+ increase in T24 cells, respectively. PKC activator PMA partially diminished A 2B AR-triggered but completely diminished β 2 -adrenergic receptor-triggered Ca 2+ increase in T24 cells. Neither β-arrestin1 nor β-arrestin2 siRNA affected A 2B AR-mediated Ca 2+ increase. Unlike in T24 cells, YM inhibited native A 2B AR-triggered calcium mobilization in MDA-MB-231 breast cancer cells. Thus, G αq/11 is vital for Ca 2+ increase in some cell types, but G iβγ -mediated Ca 2+ signaling can be Gα q/11 -dependent or independent based on cell type and receptor activated. Besides G proteins, PKC also modulates cytosolic Ca 2+ increase depending on cell type and receptor.

N-BEATS Deep Learning Architecture for Agricultural Commodity Price Forecasting - G. H. Harish Nayak; Md Wasi Alam; G. Avinash; K. N. Singh; Mrinmoy Ray; Rajeev Ranjan Kumar (Potato Research, 2025)

Efficacy of unbaited and baited green multi-funnel traps for detection of Agrilus species and other wood-boring beetle taxa - Giacomo Santoiemma; Jon Sweeney; Everett G. Booth; Giacomo Cavaletto; Gianfranco Curletti; Sarah M. Devine; Joseph A. Francese; Emily K. L. Franzen; Filippo Giannone; Mischa Giasson; Jerzy M. Gutowski; Cory Hughes; et al. (Journal of Pest Science, 2025)
Semiochemical-baited traps are a key component of post-border surveillance for detection of non-native and potentially invasive bark and wood-boring beetles (Buprestidae, Cerambycidae, Curculionidae: Scolytinae) at risk of introduction in untreated woody materials used in global trade. Because the particular species that may arrive with imported goods is unknown, plant protection agencies need trapping protocols that effectively survey all three taxa. Baiting traps with host volatiles and aggregation/sex pheromones of longhorn beetles increases efficacy of detecting Cerambycidae and Scolytinae, but its effect on detection of Agrilus species and other jewel beetles is unknown. In this multi-country trapping study we found that the addition of ethanol and common aggregation/sex pheromones of longhorn beetles to green multi-funnel traps placed in the mid-upper forest canopy had negative effects on abundance of Agrilus species and other jewel beetles collected but no effect on their species richness, and significant positive effects on species richness and abundance of Cerambycidae and Scolytinae. Baiting green canopy traps with longhorn beetle pheromones increased the efficacy of traps for detecting total target taxa of bark and wood-boring beetles at risk of international movement in untreated woody materials. This information is beneficial for the design of multi-taxa surveys, potentially saving money and resources without decreasing trapping efficacy.

Equine welfare assessment skills certification course - R. Stewart; B. Wassel; A. Best; L. Ray; B. McGonagill; B. Jackson; P. Sapp; K. Duberstein (Journal of Equine Veterinary Science, 2025)

Assessment of compressed natural gas as an alternative transportation fuel in reducing CO2 emission: a case of Agartala city - Ashish K. Reji; Bulti Das; Tuhin Kanti Ray; Eshita Boral (Environment, Development and Sustainability, 2025)

Genome-wide association study on root traits under non-stress and osmotic stress conditions to improve drought tolerance in rice (Oryza sativa Lin.) - Akshay Sureshrao Sakhare; Sudhir Kumar; Ranjith K. Ellur; G. D. Prahalada; Suneetha Kota; Ranjeet Ranjan Kumar; Soham Ray; Baidya Nath Mandal; Viswanathan Chinnusamy (Acta Physiologiae Plantarum, 2025)

Enhancing soil arsenic immobilization with organic and inorganic amendments: insights from sorption–desorption study - Md Basit Raza; Siba Prasad Datta; Debasis Golui; Mandira Barman; Prasenjit Ray; Devi Upadhyay; Rahul Mishra; Arkaprava Roy; Amit K. Dash (Environmental Monitoring and Assessment, 2024)

Simultaneous folate fortification and pesticide residue degradation in finger millet (Eleusine coracana) via malting and Lactiplantibacillus plantarum-mediated fermentation - Priyadarshini P. Nayak; Rudra P. Das; Sachin K. Mahanta; Abhishek Singh; Ajit K. Dhal; Rajani Kanta Mahapatra; Luna Goswami; Lopamudra Ray; Sunil K. Behera; Elna M. Buys; Sandeep K. Panda (Food Bioscience, 2024)

Metal cation and crystal lattice water molecule stabilized highly mesoporous manganese oxide network for excellent durable electrode in sodium-ion storage - Ramu Manikandan; C. Justin Raj; Hyun Jung; John D. Rodney; Subhasmita Ray; Antonysamy Dennyson Savariraj; Periyasamy Sivakumar; K. Karuppasamy; Byung Chul Kim; Jae-Min Oh (Chemical Engineering Journal, 2024)

Genetic and functional modulation by agonist MRS5698 and allosteric enhancer LUF6000 at the native A3 adenosine receptor in HL-60 cells - Zhan-Guo Gao; Weiping Chen; Ray R. Gao; Jonathan Li; Dilip K. Tosh; John A. Hanover; Kenneth A. Jacobson (Purinergic Signalling, 2024)
The A 3 adenosine receptor (AR) is an important inflammatory and immunological target. However, the underlying mechanisms are not fully understood. Here, we report the gene regulation in HL-60 cells treated acutely with highly selective A 3 AR agonist MRS5698, positive allosteric modulator (PAM) LUF6000, or both. Both pro- and anti-inflammatory genes, such as IL-1a, IL-1β, and NFκBIZ, are significantly upregulated. During our observations, LUF6000 alone produced a lesser effect, while the MRS5698 + LUF6000 group demonstrated generally greater effects than MRS5698 alone, consistent with allosteric enhancement. The number of genes up- and down-regulated are similar. Pathway analysis highlighted the critical involvement of signaling molecules, including IL-6 and IL-17. Important upstream regulators include IL-1a, IL-1β, TNF-α, NF-κB, etc. PPAR, which modulates eicosanoid metabolism, was highly downregulated by the A 3 AR agonist. Considering previous pharmacological results and mathematical modeling, LUF6000’s small enhancement of genetic upregulation suggested that MRS5698 is a nearly full agonist, which we demonstrated in both cAMP and calcium assays. The smaller effect of LUF6000 on MRS5698 in comparison to its effect on Cl-IB-MECA was shown in both HL-60 cells endogenously expressing the human (h) A 3 AR and in recombinant hA 3 AR-expressing CHO cells, consistent with its HL-60 cell genetic regulation patterns. In summary, by using both selective agonists and PAM, we identified genes that are closely relevant to immunity and inflammation to be regulated by A 3 AR in differentiated HL-60 cells, a cell model of neutrophil function. In addition, we demonstrated the previously uncharacterized allosteric signaling-enhancing effect of LUF6000 in cells endogenously expressing the hA 3 AR.

Trends in Arctic-nesting loon (Gavia spp.) populations in North America - Ingrid L. Pollet; Sarah E. Gutowsky; Ray T. Alisauskas; William Harvey; Dana K. Kellett; Kristen M. Lalla; Josée Lefebvre; Jake Russell-Mercier; Jennifer F. Provencher; Emily D. Silverman; Paul A. Smith; Mark L. Mallory (Polar Biology, 2024)

Efficacy of trapping protocols for Agrilus jewel beetles: a multi-country assessment - Giacomo Santoiemma; David Williams; Everett G. Booth; Giacomo Cavaletto; James Connell; Gianfranco Curletti; Maarten de Groot; Sarah M. Devine; Abigail Enston; Joseph A. Francese; Emily K. L. Franzen; Mischa Giasson; et al. (Journal of Pest Science, 2024)
The genus Agrilus is one of the most diverse insect genera worldwide. The larval feeding activity causes extensive damage in both forests and orchards. In addition, more than 30 species have been introduced outside their native range so far, including the emerald ash borer Agrilus planipennis Fairmaire. Thus, the availability of efficient trapping protocols for early detection of Agrilus species at entry points is of utmost importance. In this study we tested whether trapping protocols developed for surveillance of A. planipennis in North America were also effective for other Agrilus species. In particular, through a multi-country assessment we compared the efficacy of detecting Agrilus species on: (i) green glue-coated prism traps vs. green Fluon-coated multi-funnel traps when baited with the green leaf volatile ( Z )-3-hexenol or left unbaited; and (ii) green multi-panel traps vs. green multi-panel traps baited with dead adult Agrilus beetles (decoys). A total of 23,481 individuals from 45 Agrilus species were caught. Trap design significantly affected both species richness and abundance of Agrilus species in several of the countries where the trapping experiments were carried out, and green prism traps outperformed green multi-funnel traps in most cases. On the contrary, the addition of a ( Z )-3-hexenol lure or dead adult beetle decoys on to traps did not improve trap catches. Our study highlights that reliable trap models to survey Agrilus species are already available, but also that there is the clear need to further investigate chemical ecology of Agrilus species to develop semiochemical lures that can improve detection efficacy.

Dynamics of sediment phosphorus in the middle and lower stretch of River Ganga, India: insight into concentration, fractionation, and environmental risk assessment of phosphorus - Ajoy Saha; B. K. Das; Nitish Kumar Tiwari; Suraj Chauhan; Chayna Jana; Mitesh Ramteke; Canciyal Johnson; Raju Baitha; Himanshu Sekhar Swain; Archisman Ray; Subhadeep Das Gupta; Pranab Gogoi; et al. (Environmental Geochemistry and Health, 2024)

Cryopurification and a Microbial Fuel Cell Process as a Combined Approach to Treat Mine-Impacted Water (Faro Mine, Yukon, Canada) - Ethan Allen; Daria Popugaeva; Carlos Munoz-Cupa; Amarjeet Bassi; Konstantin Kreyman; Ajay K. Ray (Mine Water and the Environment, 2024)

Mixed-Method Heat Acclimation Induces Heat Adaptations in International Triathletes Without Training Modification - Carl A. James; Ashley G. B. Willmott; C. W. Daniel Lee; T. K. Gabriel Pun; Ray Tai; Oliver R. Gibson (Journal of Science in Sport and Exercise, 2024)
Purpose Heat acclimation (HA) kinetics often necessitates that the intervention is conducted in the weeks immediately preceding athletic competitions, potentially interfering with a training taper. Therefore, we investigated the efficacy of a mixed-method HA protocol, superimposed over planned external training loads, during the 3-weeks prior to the 2022 U23 World Triathlon Championships. Methods Six international triathletes completed 8 pre-competition HA sessions (5 active: running/cycling, 3 passive: hot water immersion [HWI]), across 2-weeks. Outdoor high-intensity training sessions were followed by 30–60 min HWI, whilst low-intensity cycling/running sessions were completed in a hot, humid environmental chamber. To assess heat adaptations, participants completed three 25 min heat stress tests (HST) involving iso-speed treadmill running (session 1 = HST1, session 5 = HST2, and session 8 = HST3). Physiological, haematological and wellbeing monitoring were conducted throughout HA. Results Reduced heart rate (~ − 6 beats/min) was observed within HST3 ( P = 0.01, η p 2 = 0.64), versus HST1 and HST2. No changes in core temperature were observed across HSTs ( P = 0.055 , η p 2 = 0.44). Sweat sodium concentration was lower by HST2 at the arm (− 23 ± 16 mmol/L, P = 0.02) and back (− 27 ± 17 mmol/L, P = 0.01). White blood cell count reduced from baseline to the end of HA ( P = 0.02, η p 2 = 0.27), but no changes were found in any other haematological markers (all P > 0.05). Perceptual wellbeing measures did not change across HA (all P > 0.05). Conclusion By HST3, seven prior mixed-method HA sessions improved markers of heat adaptation (exercising HR and sweat concentration) within international triathletes. Mixed-method HA may be implemented without modifying training load, with no apparent detrimental effects on athlete health or training stress markers.

Editorial: Research advances from Larsemann Hills, Antarctica: International cooperation and future prospects (Part-2) - Anand K. Singh; Shailendra Saini; Yogesh Ray; Svetlana Grigoreva; Xiangbin Cui; Xianglan Li; Rahul Mohan; M. Javed Beg; Rasik Ravindra (Polar Science, 2024)

Performance monitoring of the wastewater system of Bharati Station, Antarctica - Rahul Kumar; N.S. Magesh; Vivek Kumar; Kirti Ranjan Das; Ariz Ahmad; Vikas Singh; Partha Sarathi Majhi; Ravi Mishra; Anand K. Singh; Shailendra Saini; Yogesh Ray (Polar Science, 2024)

Modelling monthly rainfall of India through transformer-based deep learning architecture - G. H. Harish Nayak; Wasi Alam; K. N. Singh; G. Avinash; Mrinmoy Ray; Rajeev Ranjan Kumar (Modeling Earth Systems and Environment, 2024)

Degradation of multiple PAHs and co-contaminants by microbial consortia and their toxicity assessment - Arfin Imam; Sunil Kumar Suman; Sonpal Vasavdutta; Shruti Chatterjee; Bhanu Prasad Vempatapu; Anjan Ray; Pankaj K. Kanaujia (Biodegradation, 2024)

Valorization of dairy side-streams for the cultivation of microalgae for value added food products - Duygu Ozcelik; Shyam Suwal; Colin Ray; Brijesh K. Tiwari; Poul Erik Jensen; Mahesha M. Poojary (Trends in Food Science & Technology, 2024)

Phosphate removal from urban stormwater runoff using Canna lily and Cyperus alternifolius-based bioretention system - Naman Jain; Shivani Yadav; Sonam Taneja; Sanak Ray; A. K. Haritash; Harsh Pipil (Sustainable Water Resources Management, 2024)

Flood risk index mapping in data scarce region by considering GIS and MCDA (FRI mapping in data scarce region by considering GIS and MCDA) - S. K. Ray (Environment, Development and Sustainability, 2024)

Effect of dietary phytase on water and fecal prokaryotic and eukaryotic microbiomes in a hybrid tilapia (Oreochromis aureus x O. niloticus) mixotrophic biofloc production system - Candis L. Ray; Jason W. Abernathy; Bartholomew W. Green; Adam R. Rivers; Kevin K. Schrader; Steven D. Rawles; Matthew E. McEntire; Miles D. Lange; Carl D. Webster (Aquaculture, 2024)

Challenges and prospects of microbial α-amylases for industrial application: a review - Patel Pratima Ashok; Diptarka Dasgupta; Anjan Ray; Sunil K. Suman (World Journal of Microbiology and Biotechnology, 2024)

Identification of Suitable Sites for Water Harvesting Structures in Jamsholaghat Sub-basin Using GIS and Multi-Criteria Decision Analysis - S. K. Ray; V. R. Desai (Journal of the Indian Society of Remote Sensing, 2024)

Identifying the groundwater potential zones in Jamsholaghat sub-basin by considering GIS and multi-criteria decision analysis - S. K. Ray (International Journal of Environmental Science and Technology, 2024)

Analysis of localized features during wet and dry rainfall episodes over southern tip of India - E. A. Resmi; B. Preethi; R. S. Ajayamohan; Pallav Ray; C. K. Unnikrishnan; S. Nita; R. K. Sumesh; J. Dharmadas (International Journal of Climatology, 2023)
The large spatial and temporal variability of wet and dry spells of the Indian Summer Monsoon (ISM) poses the great challenge in understanding and predicting monsoonal rainfall. This challenge is further exacerbated over smaller regions, such as the southern tip of India, which receives the first spell of ISM rainfall. In this study, the characteristic features and possible precursors for wet and dry spells of rainfall over the southern tip of India are investigated. We also explore the variability in monsoon low‐level jet (LLJ) in relation to wet and dry spells over a coastal station Thiruvananthapuram (8.48°N, 76.95°E) in southwest India using in situ observations and other ancillary datasets. The results show that a wet spell spanning 3–4 days contributes about 30% of seasonal rainfall. Wet spells are characterized by westerly wind anomaly in the southern tip of India and easterly wind anomaly in northern India, leading to anomalous cyclonic vorticity over the Indian subcontinent. The opposite happens during dry spells. These characteristics are prominent from 2 days prior to the initiation of the spells, suggesting they may be used as precursors for forecasting wet and dry spells over Thiruvananthapuram. Analysis of low‐ to mid‐tropospheric (2 and 4 km) humidity reveals significant moistening (drying) during wet (dry) spells. Yet, both wet and dry spells experience humid (>80%) boundary layer. The differences in mid‐level humidity and thermodynamical structures between wet and dry spells seem to contribute to distinct rainfall characteristics over the southern tip of India. These results indicate that the use of in situ observations along with large‐scale reanalysis datasets may provide valuable information on the precursors for wet and dry spells over the southern tip of India, which can help both in regional‐ and city‐level planning and management of water resources.

Editorial: Research advances from Larsemann Hills, Antarctica: International cooperation and future prospects - Anand K. Singh; Shailendra Saini; Yogesh Ray; Svetlana Grigoreva; Xiangbin Cui; Xianglan Li; Rahul Mohan; M. Javed Beg; Rasik Ravindra (Polar Science, 2023)

CRISPR-Cas9 for sustainable food production: Impacts, recent advancements and future perspectives - Suryapratap Ray; Sneha K; Chitra Jangid (Food and Humanity, 2023)

The status of the CRISPR/Cas9 research in plant–nematode interactions - Tushar K. Dutta; Soham Ray; Victor Phani (Planta, 2023)

High uncertainty in fish bioenergetics impedes precision of fish-mediated carbon transport estimates into the ocean’s twilight zone - Helena McMonagle; Joel K. Llopiz; Ray Hilborn; Timothy E. Essington (Progress in Oceanography, 2023)

Pb-Pb age of the Gotan Limestone, Marwar Supergroup: Implications for Ediacaran-Cambrian transition events in the peninsular India - Bivin G. George; Milan K. Mahala; Jyotiranjan S. Ray (Precambrian Research, 2023)

The application of freezing technology for zinc removal from Faro pit mine-impacted water, Yukon, Canada - Daria Popugaeva; Ethan Allen; Matt Corriveau; Sruthee Govindaraj; Konstantin Kreyman; Ajay K. Ray (Cold Regions Science and Technology, 2023)

Pestalotiopsis leaf spot: an important foliar disease in cashewnut seedling incited by Pestalotiopsis oxyanthi in West Bengal, India - Rakesh Patsa; Subhendu Jash; Subrata Dutta; Ashis Roy Barman; Mini Poduval; Sujit K. Ray (Indian Phytopathology, 2023)

Benzo(ghi)perylene (BgP) a black tattoo ingredient induced skin toxicity via direct and indirect mode of DNA damage under UVA irradiation - Sandeep Negi; Saumya Shukla; Sunil Kumar Patel; Apeksha Vikram; Prakriti Gaur; Mohd Danish Kamar; Diksha Pathania; Sumana Y. Kotian; Madhu Bala; Priyanka Rana; Lakshmi Bala; Akhilesh K. Yadav; et al. (Chemico-Biological Interactions, 2023)

Sedimentary ancient DNA: a new paleogenomic tool for reconstructing the history of marine ecosystems - Ngoc-Loi Nguyen; Dhanushka Devendra; Natalia Szymańska; Mattia Greco; Inès Barrenechea Angeles; Agnes K. M. Weiner; Jessica Louise Ray; Tristan Cordier; Stijn De Schepper; Jan Pawłowski; Joanna Pawłowska (Frontiers in Marine Science, 2023)
Sedimentary ancient DNA ( seda DNA) offers a novel retrospective approach to reconstructing the history of marine ecosystems over geological timescales. Until now, the biological proxies used to reconstruct paleoceanographic and paleoecological conditions were limited to organisms whose remains are preserved in the fossil record. The development of ancient DNA analysis techniques substantially expands the range of studied taxa, providing a holistic overview of past biodiversity. Future development of marine seda DNA research is expected to dramatically improve our understanding of how the marine biota responded to changing environmental conditions. However, as an emerging approach, marine seda DNA holds many challenges, and its ability to recover reliable past biodiversity information needs to be carefully assessed. This review aims to highlight current advances in marine seda DNA research and to discuss potential methodological pitfalls and limitations.

Inhaled Adjunct Therapy with Second-Line Drug Candidates for Dose Reduction in Chemotherapeutic Regimens for Multi-drug-Resistant Tuberculosis - Sonia Verma; Nils-Jorgen K. Dal; Ashish Srivastava; Reena Bharti; D. V. Siva Reddy; Hasham Shafi Sofi; Trisha Roy; Khushboo Verma; Sunil K. Raman; Lubna Azmi; Lipika Ray; Madhav N. Mugale; et al. (AAPS PharmSciTech, 2023)

Structure and composition of natural ferrihydrite nano-colloids in anoxic groundwater - Maya Engel; Vincent Noël; Samuel Pierce; Libor Kovarik; Ravi K. Kukkadapu; Juan S. Lezama Pacheco; Odeta Qafoku; J. Ray Runyon; Jon Chorover; Weijiang Zhou; John Cliff; Kristin Boye; et al. (Water Research, 2023)

World Association for the Advancement of Veterinary Parasitology (W.A.A.V.P.) guideline for diagnosing anthelmintic resistance using the faecal egg count reduction test in ruminants, horses and swine - Ray M. Kaplan; Matthew J. Denwood; Martin K. Nielsen; Stig M. Thamsborg; Paul R. Torgerson; John S. Gilleard; Robert J. Dobson; Jozef Vercruysse; Bruno Levecke (Veterinary Parasitology, 2023)

Modelling crop yield and harvest index: the role of carbon assimilation and allocation parameters - Hector Camargo-Alvarez; Robert J. R. Elliott; Stefan Olin; Xuhui Wang; Chenzhi Wang; Deepak K. Ray; Thomas A. M. Pugh (Modeling Earth Systems and Environment, 2023)
Crop yield improvement during the last decades has relied on increasing the ratio of the economic organ to the total aboveground biomass, known as the harvest index (HI). In most crop models, HI is set as a parameter; this empirical approach does not consider that HI not only depends on plant genotype, but is also affected by the environment. An alternative is to simulate allocation mechanistically, as in the LPJ-GUESS crop model, which simulates HI based on daily growing conditions and the crop development stage. Simulated HI is critical for agricultural research due to its economic importance, but it also can validate the robust representation of production processes. However, there is a challenge to constrain parameter values globally for the allocation processes. Therefore, this paper aims to evaluate the sensitivity of yield and HI of wheat and maize simulated with LPJ-GUESS to eight production allocation-related parameters and identify the most suitable parameter values for global simulations. The nitrogen demand reduction after anthesis, the minimum leaf carbon to nitrogen ratio (C:N) and the range of leaf C:N strongly affected carbon assimilation and yield, while the retranslocation of labile stem carbon to grains and the retranslocation rate of nitrogen and carbon from vegetative organs to grains after anthesis mainly influenced HI. A global database of observed HI for both crops was compiled for reference to constrain simulations before calibrating parameters for yield against reference data. Two high- and low-yielding maize cultivars emerged from the calibration, whilst spring and winter cultivars were found appropriate for wheat. The calibrated version of LPJ-GUESS improved the simulation of yield and HI at the global scale for both crops, providing a basis for future studies exploring crop production under different climate and management scenarios.

Correction to: Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)

Cytogenetic Diversity in Scilloideae (Asparagaceae): a Comprehensive Recollection and Exploration of Karyo-Evolutionary Trends - Sayantani Nath; Sayantika Sarkar; Sayali D. Patil; Partha Sarathi Saha; Manoj M. Lekhak; Sudipta Ray; Satyawada Rama Rao; S. R. Yadav; R. C. Verma; Manoj K. Dhar; S. N. Raina; Sumita Jha (The Botanical Review, 2023)

An alternative view on size and impact history of Ramgarh Crater, India: Evidence from high-resolution remote sensing imagery and gravity data - Saumitra Misra; Pankaj K Srivastava; Sambhunath Ghosh; Arnab K Das; Shikendha K Dey; Dwijesh Ray (Journal of Earth System Science, 2023)

Rise and fall of SARS-CoV-2 variants in Rotterdam: Comparison of wastewater and clinical surveillance - Ray W. Izquierdo-Lara; Leo Heijnen; Bas B. Oude Munnink; Claudia M.E. Schapendonk; Goffe Elsinga; Jeroen Langeveld; Johan Post; Divyae K. Prasad; Christian Carrizosa; Frederic Been; Janko van Beek; Remy Schilperoort; et al. (Science of The Total Environment, 2023)

C-Sr-Pb isotope systematics of the carbonate sequences of Kaladgi Supergroup, India: Implications for basin evolution and correlation with Proterozoic global events - Bivin G. George; Jyotiranjan S. Ray; Shilpa Patil Pillai; Milan K. Mahala; Sanjeev Kumar; Vivek S. Kale (Precambrian Research, 2023)

Structural Changes in Liposomal Vesicles in Association with Sodium Taurodeoxycholate - Deepak Kumar; Abhishek Suna; Debes Ray; Vinod K. Aswal; Pratap Bahadur; Sanjay Tiwari (AAPS PharmSciTech, 2023)

Microbathymetry inferences from two AUV dives over a short segment of the Central Indian Ridge between 10°18′ and 10°57′S, Indian Ocean - K. A. Kamesh Raju; V. Yatheesh; A. Srinivas Rao; L. Surya Prakash; Durbar Ray; Abhay Mudholkar; Kiranmai Samudrala; Nico Augustin; P. John Kurian (Geo-Marine Letters, 2023)

Correction to: Pyrene remediation by Trametes maxima: an insight into secretome response and degradation pathway - Arfin Imam; Sunil Kumar Suman; Bhanu Prasad Vempatapu; Deependra Tripathi; Anjan Ray; Pankaj K. Kanaujia (Environmental Science and Pollution Research, 2023)

A statistical framework for calculating prospective sample sizes and classifying efficacy results for faecal egg count reduction tests in ruminants, horses and swine - Matthew J. Denwood; Ray M. Kaplan; Iain J. McKendrick; Stig M. Thamsborg; Martin K. Nielsen; Bruno Levecke (Veterinary Parasitology, 2023)

Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)
Global pollinator declines threaten food production and natural ecosystems. The drivers of declines are complicated and driven by numerous factors such as pesticide use, loss of habitat, rising pathogens due to commercial bee keeping and climate change. Halting and reversing pollinator declines will require a multidisciplinary approach and international cooperation. Here, we summarize 20 presentations given in the symposium ‘Protecting pollinators and our food supply: Understanding and managing threats to pollinator health’ at the 19th Congress of the International Union for the Study of Social Insects in San Diego, 2022. We then synthesize the key findings and discuss future research areas such as better understanding the impact of anthropogenic stressors on wild bees.

Assessment of extreme rainfall through statistical process control-I chart - N S Abeysingha; K M Kularathna; A M K R Bandara; Ram L Ray (Journal of Earth System Science, 2023)

Getting the most out of maths: How to coordinate mathematical modelling research to support a pandemic, lessons learnt from three initiatives that were part of the COVID-19 response in the UK - Ciara E. Dangerfield; I. David Abrahams; Chris Budd; Matt Butchers; Michael E. Cates; Alan R. Champneys; Christine S.M. Currie; Jessica Enright; Julia R. Gog; Alain Goriely; T. Déirdre Hollingsworth; Rebecca B. Hoyle; et al. (Journal of Theoretical Biology, 2023)

Morphological changes currently occurring in sand-filled gully channels on Mars: Implications for the role of substrates inside channels - Rishitosh K. Sinha; Dwijesh Ray (Icarus, 2023)

Proteomic response of Pseudomonas aeruginosa IIPIS-8 during rapid and efficient degradation of naphthalene - Arfin Imam; Sunil Kumar Suman; Praveen Singh; Bhanu Prasad Vempatapu; Deependra Tripathi; Anjan Ray; Pankaj K. Kanaujia (Environmental Research, 2023)

Effect of ferrate pretreatment on anaerobic digestibility of primary sludge spiked with resin acids - Sreejon Das; Kyriakos Manoli; Virender K. Sharma; Martha Dagnew; Madhumita B. Ray (Environmental Science and Pollution Research, 2022)

Technology Forecasting for Envisioning Bt Technology Scenario in Indian Agriculture - Mrinmoy Ray; V. Ramasubramanian; K. N. Singh; Santosha Rathod; Ravindra Singh Shekhawat (Agricultural Research, 2022)

Fuzzy rule–based weighted space–time autoregressive moving average models for temperature forecasting - Amit Saha; K. N. Singh; Mrinmoy Ray; Santosha Rathod; Makrand Dhyani (Theoretical and Applied Climatology, 2022)

A GIS-based Spatial Prediction of Landslide Hazard Zones and Mapping in an Eastern Himalayan Hilly Region Using Large Scale Soil Mapping and Analytical Hierarchy Process - R. Srinivasan; D. Vasu; S. Amar Suputhra; Rajendra Hegde; S. K. Ray; S. K. Singh (Journal of the Indian Society of Remote Sensing, 2022)

Petrology and geochemistry of Bhanjada Bet phonolites, Kutch, Gujarat in Western Deccan Province: Possibility of a mantle-derived primary phonolite magma - Debarun Mukherjee; Arijit Ray; Dalim K Paul; Kuhu Chakraborty; Mahesh Thakkar; Gaurav Chouhan (Journal of Earth System Science, 2022)

Pyrene remediation by Trametes maxima: an insight into secretome response and degradation pathway - Arfin Imam; Sunil Kumar Suman; Bhanu Prasad Vempatapu; Deependra Tripathi; Anjan Ray; Pankaj K. Kanaujia (Environmental Science and Pollution Research, 2022)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Variation in migration behaviors used by Arctic Terns (Sterna paradisaea) breeding across a wide latitudinal gradient - Joanna B. Wong; Simeon Lisovski; Ray T. Alisauskas; Willow English; Autumn-Lynn Harrison; Dana K. Kellett; Mark Maftei; Avery Nagy-MacArthur; Robert A. Ronconi; Paul A. Smith; Mark L. Mallory; Marie Auger-Méthé (Polar Biology, 2022)

Remote sensing of cytotype and its consequences for canopy damage in quaking aspen - Benjamin Blonder; Philip G. Brodrick; James A. Walton; Katherine Dana Chadwick; Ian K. Breckheimer; Suzanne Marchetti; Courtenay A. Ray; Karen E. Mock (Global Change Biology, 2022)
Mapping geographic mosaics of genetic variation and their consequences via genotype x environment interactions at large extents and high resolution has been limited by the scalability of DNA sequencing. Here, we address this challenge for cytotype (chromosome copy number) variation in quaking aspen, a drought‐impacted foundation tree species. We integrate airborne imaging spectroscopy data with ground‐based DNA sequencing data and canopy damage data in 391 km 2 of southwestern Colorado. We show that (1) aspen cover and cytotype can be remotely sensed at 1 m spatial resolution, (2) the geographic mosaic of cytotypes is heterogeneous and interdigitated, (3) triploids have higher leaf nitrogen, canopy water content, and carbon isotope shifts (δ 13 C) than diploids, and (4) canopy damage varies among cytotypes and depends on interactions with topography, canopy height, and trait variables. Triploids are at higher risk in hotter and drier conditions.

Disorders of Tetrahydrobiopterin Metabolism: Experience from South India - Somdattaa Ray; Hansashree Padmanabha; Vykuntaraju K. Gowda; Rohan Mahale; Rita Christopher; Shruthy Sreedharan; Debjyoti Dhar; Mahesh Kamate; Madhu Nagappa; Maya Bhat; Rammurthy Anjanappa; Gautham Arunachal; et al. (Metabolic Brain Disease, 2022)

Challenges of forecasting rainfall associated with tropical cyclones in India - Kamaljit Ray; S. Balachandran; Sushil K. Dash (Meteorology and Atmospheric Physics, 2022)

Applications of Advanced Geospatial Technology for Expansion of Area under Horticultural Crops in North Eastern Region of India - B. K. Handique; C. Goswami; P. Jena; F. Dutta; R. Samiam; I. Nongrum; D. Jha; P. L. N. Raju; C. R. Deka; R. Sarma; K. Sarmah; H. K. Dutta; et al. (Journal of the Indian Society of Remote Sensing, 2022)

Stable isotope and geochemical evidence on sources and mechanisms of groundwater recharge in the Nalanda-Rajgir Region of Eastern India - Satya Narayan Sethy; Tajdarul Hassan Syed; Rambabu Singh; Ranjan K. Ray; Bhagirathi Behera (Arabian Journal of Geosciences, 2022)

Comparative transcriptome profiling reveals the basis of differential sheath blight disease response in tolerant and susceptible rice genotypes - Pankajini Samal; Kutubuddin A. Molla; Archana Bal; Soham Ray; Harekrushna Swain; Ansuman Khandual; Pritiranjan Sahoo; Motilal Behera; Sarika Jaiswal; Asif Iquebal; Mridul Chakraborti; Lambodar Behera; et al. (Protoplasma, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Regulation of autophagy as a therapeutic option in glioblastoma - Amanda J. Manea; Swapan K. Ray (Apoptosis, 2021)

A Review of the Opportunities and Challenges for Using Remote Sensing for Management of Surface-Canopy Forming Kelps - Kyle C. Cavanaugh; Tom Bell; Maycira Costa; Norah E. Eddy; Lianna Gendall; Mary G. Gleason; Margot Hessing-Lewis; Rebecca Martone; Meredith McPherson; Ondine Pontier; Luba Reshitnyk; Rodrigo Beas-Luna; et al. (Frontiers in Marine Science, 2021)
Surface-canopy forming kelps provide the foundation for ecosystems that are ecologically, culturally, and economically important. However, these kelp forests are naturally dynamic systems that are also threatened by a range of global and local pressures. As a result, there is a need for tools that enable managers to reliably track changes in their distribution, abundance, and health in a timely manner. Remote sensing data availability has increased dramatically in recent years and this data represents a valuable tool for monitoring surface-canopy forming kelps. However, the choice of remote sensing data and analytic approach must be properly matched to management objectives and tailored to the physical and biological characteristics of the region of interest. This review identifies remote sensing datasets and analyses best suited to address different management needs and environmental settings using case studies from the west coast of North America. We highlight the importance of integrating different datasets and approaches to facilitate comparisons across regions and promote coordination of management strategies.

Novel Metabolites as Potential Indicators of Ischemic Infarction Volume: a Pilot Study - Evgeny V. Sidorov; Cynthia Bejar; Chao Xu; Bappaditya Ray; David Gordon; Juliane Chainakul; Dharambir K. Sanghera (Translational Stroke Research, 2021)

Breeding latitude is associated with the timing of nesting and migration around the annual calendar among Purple Martin (Progne subis) populations - L. R. Neufeld; S. Muthukumarana; J. D. Fischer; J. D. Ray; J. Siegrist; K. C. Fraser (Journal of Ornithology, 2021)

A satellite-based comprehensive observation of glaciological characteristics of Shunkalpa (Ralam) Glacier, Central Himalaya, India - Pratima Pandey; Debangshu Banerjee; Prashant K Champati Ray (Journal of Earth System Science, 2021)

Removal of textile dyes from water by jute stick activated carbon: process optimization and isotherm studies - R. K. Ghosh; D. P. Ray; A. Tewari; I. Das (International Journal of Environmental Science and Technology, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Yeast-based screening of cancer mutations in the DNA damage response protein Mre11 demonstrates importance of conserved capping domain residues - Caitlin Harris; Jessica Savas; Sreerupa Ray; Erin K. Shanle (Molecular Biology Reports, 2021)

Seasonal occurrence and sexual segregation of great white sharks Carcharodon carcharias in Mossel Bay, South Africa - Hannah R. Milankovic; Nicholas D. Ray; Louise K. Gentle; Christo Kruger; Esther Jacobs; Craig J. Ferreira (Environmental Biology of Fishes, 2021)
The seasonal occurrence and temporal sexual segregation of great white sharks Carcharodon carcharias have been widely documented in various temperate and sub-tropical waters across the globe. Yet, there is limited understanding of the relationship between the life stages and habitat use of C. carcharias , particularly in the Southern Cape. In this study, we investigated the population dynamics of C. carcharias in Mossel Bay, South Africa, between 2009 and 2013, using skipper logbooks and citizen research data obtained by a cage-diving vessel. A total of 3064 sharks, ranging in life history stages from young-of-the-year to subadult, were sighted during 573 trips. Juveniles dominated the sightings throughout the study, and there was marked sexual segregation, with females dominating the total sightings of sharks. C. carcharias were most abundant during the cooler, winter season, with females differing in abundance seasonally and males maintaining a low abundance throughout the year but peaking in the winter. In addition, sea surface temperature was the best indicator of C. carcharias presence. Abundance was greatest when vertical water visibility exceeded 3 m, with cloud cover influencing overall abundance negatively. Likely reasoning for the aggregation of C. carcharias in Mossel Bay includes the favourable conditions and abundance of food. Juvenile sharks may also utilise this area as a training ground to learn from larger conspecifics. This research demonstrates that information on population size and structure of C. carcharias can be obtained effectively through a compilation of logbook and citizen science data to assess and identify potential critical habitats in the quest to develop appropriate management strategies. This research also shows value in commercial cage-diving operations deriving international data sets needed to assess global populations of C. carcharias .

Assessment of groundwater depletion–induced land subsidence and characterisation of damaging cracks on houses: a case study in Mohali-Chandigarh area, India - Neha Kadiyan; R. S. Chatterjee; Pranshu Pranjal; Pankaj Agrawal; S. K. Jain; M. L. Angurala; A. K. Biyani; M. S. Sati; Dheeraj Kumar; Ashutosh Bhardwaj; P. K. Champati Ray (Bulletin of Engineering Geology and the Environment, 2021)

Accuracy assessment of global internal-tide models using satellite altimetry - Loren Carrere; Brian K. Arbic; Brian Dushaw; Gary Egbert; Svetlana Erofeeva; Florent Lyard; Richard D. Ray; Clément Ubelmann; Edward Zaron; Zhongxiang Zhao; Jay F. Shriver; Maarten Cornelis Buijsman; et al. (Ocean Science, 2021)
Altimeter measurements are corrected for several geophysical parameters in order to access ocean signals of interest, like mesoscale or sub-mesoscale variability. The ocean tide is one of the most critical corrections due to the amplitude of the tidal elevations and to the aliasing phenomena of high-frequency signals into the lower-frequency band, but the internal-tide signatures at the ocean surface are not yet corrected globally. Internal tides can have a signature of several centimeters at the surface with wavelengths of about 50–250 km for the first mode and even smaller scales for higher-order modes. The goals of the upcoming Surface Water Ocean Topography (SWOT) mission and other high-resolution ocean measurements make the correction of these small-scale signals a challenge, as the correction of all tidal variability becomes mandatory to access accurate measurements of other oceanic signals. In this context, several scientific teams are working on the development of new internal-tide models, taking advantage of the very long altimeter time series now available, which represent an unprecedented and valuable global ocean database. The internal-tide models presented here focus on the coherent internal-tide signal and they are of three types: empirical models based upon analysis of existing altimeter missions, an assimilative model and a three-dimensional hydrodynamic model. A detailed comparison and validation of these internal-tide models is proposed using existing satellite altimeter databases. The analysis focuses on the four main tidal constituents: M2, K1, O1 and S2. The validation process is based on a statistical analysis of multi-mission altimetry including Jason-2 and Cryosphere Satellite-2 data. The results show a significant altimeter variance reduction when using internal-tide corrections in all ocean regions where internal tides are generating or propagating. A complementary spectral analysis also gives some estimation of the performance of each model as a function of wavelength and some insight into the residual non-stationary part of internal tides in the different regions of interest. This work led to the implementation of a new internal-tide correction (ZARON'one) in the next geophysical data records version-F (GDR-F) standards.

Attempted Isolation of Cryptococcus Species and Incidental Isolation of Exophiala dermatitidis from Human Oral Cavities - Caroline P. Toberna; Jessica J. F. Kram; Eric T. Beck; Sommer Ray; Tyler Gavinski; Alana K. Sterkel; Dennis J. Baumgardner (Mycopathologia, 2020)

Monitoring agricultural drought using combined drought index in India - N Chattopadhyay; K Malathi; Nivedita Tidke; S D Attri; Kamaljit Ray (Journal of Earth System Science, 2020)

Mapping quantitative trait loci (QTL) for plant nitrogen isotope ratio (δ15N) in soybean - Sumandeep K. Bazzer; Jeffery D. Ray; James R. Smith; Felix B. Fritschi; Larry C. Purcell (Euphytica, 2020)

A hybrid spatio-temporal modelling: an application to space-time rainfall forecasting - Amit Saha; K. N. Singh; Mrinmoy Ray; Santosha Rathod (Theoretical and Applied Climatology, 2020)

Cell-Permeable Calpain Inhibitor SJA6017 Provides Functional Protection to Spinal Motoneurons Exposed to MPP+ - Supriti Samantaray; Varduhi H. Knaryan; Angelo M. Del Re; John J. Woodward; Donald C. Shields; Mitsuyoshi Azuma; Jun Inoue; Swapan K. Ray; Naren L. Banik (Neurotoxicity Research, 2020)

Success Bias and Inflation Bias After Planning and Communicating Emotional Support - Colter D. Ray; Kory Floyd; Paul A. Mongeau; Ashley K. Randall (Journal of Cancer Education, 2020)

Elevated turbidity and dissolved manganese in deep water column near 10°47’S Central Indian Ridge: studies on hydrothermal activities - Durbar Ray; K. A. KameshRaju; A. Srinivas Rao; L. SuryaPrakash; Abhay V. Mudholkar; V. Yatheesh; Kiranmai Samudrala; Dalayya Kota (Geo-Marine Letters, 2020)

A rapid and sensitive method to detect SARS-CoV-2 virus using targeted-mass spectrometry - Praveen Singh; Rahul Chakraborty; Robin Marwal; V. S. Radhakrishan; Akash Kumar Bhaskar; Himanshu Vashisht; Mahesh S. Dhar; Shalini Pradhan; Gyan Ranjan; Mohamed Imran; Anurag Raj; Uma Sharma; et al. (Journal of Proteins and Proteomics, 2020)

Life cycle assessment comparison of wooden and plastic pallets in the grocery industry - Sebastian K. Anil; Junfeng Ma; Gül E. Kremer; Charles David Ray; Shirin M. Shahidi (Journal of Industrial Ecology, 2020)
Wooden and plastic pallets are used extensively in global trade to transport finished goods and products. This article compares the life cycle performance of treated wooden and plastic pallets through a detailed cradle‐to‐grave life cycle assessment (LCA), and conducts an analysis of the various phytosanitary treatments. The LCA investigates and evaluates the environmental impacts due to the resources consumed and emissions of the product throughout its life cycle. The environmental impacts of the pallets are compared on a one‐trip basis and a 100,000‐trips basis. Impact categories are chosen with respect to environmental concerns. The results show that on a one‐trip basis, wooden pallets with conventional and radio frequency (RF) heat treatment incur an overall carbon footprint of 71.8% and 80.3% lower, respectively, than plastic pallets during their life cycle; and in comparison with wooden pallets treated with methyl bromide fumigation, they incur 20% and 30% less overall carbon footprint. Theoretical calculations of the resource consumption and emissions of RF treatment of pallets suggest that dielectric technology may provide a lower‐carbon alternative to both current ISPM 15‐approved treatments and to plastic pallets. Methyl bromide fumigation (15.95 kg CO 2 equivalent [eq.]) has a larger carbon footprint than conventional heat treatment (12.69 kg CO 2 eq.) of pallets. For the 100,000‐trips basis, the differences are even more significant. The results recommend that wooden pallets are more environmentally friendly than plastic pallets, and conventional and RF heat treatment for wooden pallets is more sustainable than methyl bromide fumigation treatment.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Identification of quantitative trait loci for carbon isotope ratio (δ13C) in a recombinant inbred population of soybean - Sumandeep K. Bazzer; Avjinder S. Kaler; Jeffery D. Ray; James R. Smith; Felix B. Fritschi; Larry C. Purcell (Theoretical and Applied Genetics, 2020)

Modeling the impact of rainfall variations and management interventions on the groundwater regime of a hard-rock terrain in central India - Ranjan K. Ray; Tajdarul H. Syed; Dipankar Saha; Bhabesh C. Sarkar (Hydrogeology Journal, 2020)

Identification and genotypic characterization of porcine teschovirus from selected pig populations in India - Pradeep K. Ray; P. A. Desingu; R. Anoopraj; R. K Singh; G. Saikumar (Tropical Animal Health and Production, 2020)

Potential carcinogenic and non-carcinogenic health hazards of metal(loid)s in food grains - Sandip Singh Bhatti; Vaneet Kumar; Anupama Kumar; Jason K. Kirby; John Gouzos; Ray Correll; Jaswinder Singh; Vasudha Sambyal; Avinash Kaur Nagpal (Environmental Science and Pollution Research, 2020)

Synergism of 4HPR and SAHA increases anti-tumor actions in glioblastoma cells - Firas Khathayer; Matthew A. Taylor; Swapan K. Ray (Apoptosis, 2020)

Effects of integrated farming system and rainwater harvesting on livelihood improvement in North-Eastern region of India compared to traditional shifting cultivation: evidence from an action research - Sanjay Kumar Ray; Dibyendu Chatterjee; D. J. Rajkhowa; S. K. Baishya; S. Hazarika; S. Paul (Agroforestry Systems, 2020)

Bioaccumulation of vanadium (V), niobium (Nb) and tantalum (Ta) in diverse mangroves of the Indian Sundarbans - R. Ray; B. Dutta; S. K. Mandal; A. G. González; O. S. Pokrovsky; T. K. Jana (Plant and Soil, 2020)

Thunderstorm dynamics through wind profiling features: the first observation by stratospheric-tropospheric radar of GU - M. Devi; S. Patgiri; A. Medhi; S. Das; M. Saikia; A. K. Barbara; S. S. Kakatkar; K. P. Ray (Natural Hazards, 2020)

The pharmacokinetics of 3-fluoroamphetamine following delivery using clinically relevant routes of administration - Ying Jiang; Azizi Ray; Mohammad Shajid Ashraf Junaid; Sonalika Arup Bhattaccharjee; Kayla Kelley; Ajay K. Banga; Bruce E. Blough; Kevin S. Murnane (Drug Delivery and Translational Research, 2020)

Prolonged Outbreak of Candida krusei Candidemia in Paediatric Ward of Tertiary Care Hospital - Harsimran Kaur; Shamanth A. Shankarnarayana; Vinaykumar Hallur; Jayashree Muralidharan; Manisha Biswal; Anup K. Ghosh; Pallab Ray; Arunaloke Chakrabarti; Shivaprakash M. Rudramurthy (Mycopathologia, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Diversity of hepatitis C virus infection among HIV-infected people who inject drugs in India - S. S. Solomon; D. Boon; S. Saravanan; A. K. Srikrishnan; C. K. Vasudevan; P. Balakrishnan; D. Persaud; S. C. Ray; S. Mehta; S. H. Mehta (VirusDisease, 2019)

Revisiting Moisture Transport During the Indian Summer Monsoon Using the Moisture River Concept - Chetana Patil; Thara Prabhakaran; K. C. Sinha Ray; Anandakumar Karipot (Pure and Applied Geophysics, 2019)

Ionic selectivity and coordinated transport of Na+ and K+ in flag leaves render differential salt tolerance in rice at the reproductive stage - Koushik Chakraborty; Krishnendu Chattaopadhyay; Lopamudra Nayak; Soham Ray; Lucina Yeasmin; Priyanka Jena; Sunanda Gupta; Sangram K. Mohanty; Padmini Swain; Ramani K. Sarkar (Planta, 2019)

Role of Apolipoprotein E, Cathepsin D, and Brain-Derived Neurotrophic Factor in Parkinson’s Disease: A Study from Eastern India - Prosenjit Pal; Tamal Sadhukhan; Subhadip Chakraborty; Sriparna Sadhukhan; Arindam Biswas; Shyamal K. Das; Kunal Ray; Jharna Ray (NeuroMolecular Medicine, 2019)

Response of tropical cyclone Phailin (2013) in the Bay of Bengal to climate perturbations - Rashmi Mittal; Mukul Tewari; Chandrasekar Radhakrishnan; Pallav Ray; Tarkeshwar Singh; Alexander K. Nickerson (Climate Dynamics, 2019)

Applications of plant ingredients for tropical and subtropical freshwater finfish: possibilities and challenges - Koushik Ghosh; Arun K. Ray; Einar Ringø (Reviews in Aquaculture, 2019)
The demand for cultured finfish has increased tremendously during the last decades, but the success of intensive farming is dependent on several factors, namely management, dietary supplementations and welfare. During the last decades, increasing demand, high price and limited supply of fishmeal have emphasized the need for alternative protein sources in aquafeeds, but plant proteins possess a series of endogenous antinutritional factors ( ANF s; e.g. protease inhibitors, tannin, mimosine, phytic acid, nonstarch polysaccharides), and they must be destroyed or inactivated. Inclusion of alternative protein sources has resulted in production losses and is a concern for farmers. However, the problem with ANF s might be solved using advanced processing techniques. The present review, focusing on tropical and subtropical freshwater finfish, will discuss findings on applications of conventional methods, as well as fermentation technology for deactivation of endogenous ANF s, and the use of probiotics with ANF degrading potential when plant ingredients are included in fish feeds.

Kinetics of carbon and nitrogen assimilation by heterotrophic microorganisms during wastewater treatment - Sanak Ray; Miklas Scholz; A. K. Haritash (Environmental Monitoring and Assessment, 2019)

Solubilization of Carbamazepine in TPGS Micelles: Effect of Temperature and Electrolyte Addition - Shubham Jain; Sonia Pandey; Priyanka Sola; Habiba Pathan; Rahul Patil; Debes Ray; Vinod K. Aswal; Pratap Bahadur; Sanjay Tiwari (AAPS PharmSciTech, 2019)

Beneficial Changes in Capsicum frutescens Due to Priming by Plant Probiotic Burkholderia spp. - Rohini Sabu; R. Aswani; K. S. Nidheesh; J.G. Ray; A. Remakanthan; E. K. Radhakrishnan (Probiotics and Antimicrobial Proteins, 2019)

Co-digestion of Biowastes to Enhance Biological Hydrogen Process by Defined Mixed Bacterial Cultures - Sanjay K. S. Patel; Subhasree Ray; Jyotsana Prakash; Ji Hyang Wee; Sang-Yong Kim; Jung-Kul Lee; Vipin Chandra Kalia (Indian Journal of Microbiology, 2019)

Probing the effect of a room temperature ionic liquid on phospholipid membranes in multilamellar vesicles - S. Mitra; D. Ray; G. Bhattacharya; R. Gupta; D. Sen; V. K. Aswal; S. K. Ghosh (European Biophysics Journal, 2019)

State of rare earth elements in the sediment and their bioaccumulation by mangroves: a case study in pristine islands of Indian Sundarban - Sanjay K. Mandal; Raghab Ray; Aridane G. González; Vasileios Mavromatis; Oleg S. Pokrovsky; Tapan K. Jana (Environmental Science and Pollution Research, 2019)

Adsorption of cadmium ions by cucumber peel in continuous mode - M. Basu; A. K. Guha; L. Ray (International Journal of Environmental Science and Technology, 2019)

Beneficial effects of fenofibrate in pulmonary hypertension in rats - Palak Galhotra; Pankaj Prabhakar; Himanshu Meghwani; Soheb A. Mohammed; Sanjay Kumar Banerjee; Sandeep Seth; Milind P. Hote; K. H. Reeta; Ruma Ray; Subir Kumar Maulik (Molecular and Cellular Biochemistry, 2018)

Targeting autophagy for combating chemoresistance and radioresistance in glioblastoma - Matthew A. Taylor; Bhaskar C. Das; Swapan K. Ray (Apoptosis, 2018)

Remote Sensing-Based Yield Forecasting for Sugarcane (Saccharum officinarum L.) Crop in India - S. K. Dubey; A. S. Gavli; S. K. Yadav; Seema Sehgal; S. S. Ray (Journal of the Indian Society of Remote Sensing, 2018)

Coated-Platelet Trends Predict Short-Term Clinical OutcomeAfter Subarachnoid Hemorrhage - Bappaditya Ray; Vijay M. Pandav; Eleanor A. Mathews; David M. Thompson; Lance Ford; Lori K. Yearout; Bradley N. Bohnstedt; Shuchi Chaudhary; George L. Dale; Calin I. Prodan (Translational Stroke Research, 2018)

Correction to: High CO2 absorption of O-carboxymethylchitosan synthesised from chitosan - Pradeep Kumar; Ekta Faujdar; Raj K. Singh; Subham Paul; Aruna Kukrety; Vijay K. Chhibber; Siddharth S. Ray (Environmental Chemistry Letters, 2018)

High CO2 absorption of O-carboxymethylchitosan synthesised from chitosan - Pradeep Kumar; Ekta Faujdar; Raj K. Singh; Subham Paul; Aruna Kukrety; Vijay K. Chhibber; Siddharth S. Ray (Environmental Chemistry Letters, 2018)

Biogenic hydrogen sulphide emissions and non-sea sulfate aerosols over the Indian Sundarban mangrove forest - D. Ganguly; R. Ray; N. Majumdar; C. Chowdhury; T. K. Jana (Journal of Atmospheric Chemistry, 2018)

Phosphorus Budget of the Sundarban Mangrove Ecosystem: Box Model Approach - R. Ray; N. Majumder; C. Chowdhury; S. Das; T. K. Jana (Estuaries and Coasts, 2018)

Ecology of Endomycorrhizal Association in Musa spp. of South India - K. S. Nidheesh; N. Valsalakumar; V. P. Potty; J. G. Ray (Symbiosis, 2018)

Replacement of a unique population of newts (Taricha granulosa mazamae) by introduced signal crayfish (Pacifastacus leniusculus) in Crater Lake, Oregon - Scott F. Girdner; Andrew M. Ray; Mark W. Buktenica; David K. Hering; Jeremy A. Mack; John W. Umek (Biological Invasions, 2018)

Transcriptomic changes in Echinochloa colona in response to treatment with the herbicide imazamox - Alice A. Wright; Rajkumar Sasidharan; Liisa Koski; Marianela Rodriguez-Carres; Daniel G. Peterson; Vijay K. Nandula; Jeffery D. Ray; Jason A. Bond; David R. Shaw (Planta, 2018)

Distribution of Trace Metals in Channel Sediment: a Case Study in South Atlantic Coast of Spain - Md. Khurshid Alam Bhuiyan; Sabrina Qureshi; Md. Masum Billah; Suresh Varma Kammella; Md. Rushna Alam; Sunuram Ray; Md. Mostafa Monwar; Abu Hena M. K. (Water, Air, & Soil Pollution, 2018)

Modulation of the Photophysical Properties of β-substituted BODIPY Dyes - Ankush B. More; Goutam Chakraborty; Soumyaditya Mula; Alok K. Ray; Nagaiyan Sekar (Journal of Fluorescence, 2018)

Erratum: Assessment of village-wise groundwater draft for irrigation: a field-based study in hard-rock aquifers of central India - R. K. Ray; T. H. Syed; Dipankar Saha; B. C. Sarkar; A. K. Patre (Hydrogeology Journal, 2017)

Assessment of village-wise groundwater draft for irrigation: a field-based study in hard-rock aquifers of central India - R. K. Ray; T. H. Syed; Dipankar Saha; B. C. Sarkar; A. K. Patre (Hydrogeology Journal, 2017)

Effect of Rainfall Variability on Rice Yield in North Eastern Hills of India: A Case Study - Deotrephy K. Dkhar; S. M. Feroze; Ram Singh; Lala I. P. Ray (Agricultural Research, 2017)

Proton Induced Modulation of ICT and PET Processes in an Imidazo-phenanthroline Based BODIPY Fluorophores - Shrikant S. Thakare; Goutam Chakraborty; Shantaram Kothavale; Soumyaditya Mula; Alok K. Ray; Nagaiyan Sekar (Journal of Fluorescence, 2017)

Stable carbon and oxygen isotope study on benthic foraminifera: Implication for microhabitat preferences and interspecies correlation - Ajoy K Bhaumik; Shiv Kumar; Shilpi Ray; G K Vishwakarma; Anil K Gupta; Pushpendra Kumar; Kalachand Sain (Journal of Earth System Science, 2017)

Migratory stopover timing is predicted by breeding latitude, not habitat quality, in a long-distance migratory songbird - A. Van Loon; J. D. Ray; A. Savage; J. Mejeur; L. Moscar; M. Pearson; M. Pearman; G. T. Hvenegaard; N. Mickle; K. Applegate; K. C. Fraser (Journal of Ornithology, 2017)

Decadal declines in avian herbivore reproduction: density‐dependent nutrition and phenological mismatch in the Arctic - Megan V. Ross; Ray T. Alisauskas; David C. Douglas; Dana K. Kellett (Ecology, 2017)
A full understanding of population dynamics depends not only on estimation of mechanistic contributions of recruitment and survival, but also knowledge about the ecological processes that drive each of these vital rates. The process of recruitment in particular may be protracted over several years, and can depend on numerous ecological complexities until sexually mature adulthood is attained. We addressed long‐term declines (23 breeding seasons, 1992–2014) in the per capita production of young by both Ross's Geese ( Chen rossii ) and Lesser Snow Geese ( Chen caerulescens caerulescens ) nesting at Karrak Lake in Canada's central Arctic. During this period, there was a contemporaneous increase from 0.4 to 1.1 million adults nesting at this colony. We evaluated whether (1) density‐dependent nutritional deficiencies of pre‐breeding females or (2) phenological mismatch between peak gosling hatch and peak forage quality, inferred from NDVI on the brood‐rearing areas, may have been behind decadal declines in the per capita production of goslings. We found that, in years when pre‐breeding females arrived to the nesting grounds with diminished nutrient reserves, the proportional composition of young during brood‐rearing was reduced for both species. Furthermore, increased mismatch between peak gosling hatch and peak forage quality contributed additively to further declines in gosling production, in addition to declines caused by delayed nesting with associated subsequent negative effects on clutch size and nest success. The degree of mismatch increased over the course of our study because of advanced vegetation phenology without a corresponding advance in Goose nesting phenology. Vegetation phenology was significantly earlier in years with warm surface air temperatures measured in spring (i.e., 25 May–30 June). We suggest that both increased phenological mismatch and reduced nutritional condition of arriving females were behind declines in population‐level recruitment, leading to the recent attenuation in population growth of Snow Geese.

A TaqMan real-time PCR assay for Rhizoctonia cerealis and its use in wheat and soil - J. W. Woodhall; M. J. Brown; K. Perkins; E. Somoza Valdeolmillos; N. Boonham; R. V. Ray (European Journal of Plant Pathology, 2017)

Mineral chemistry of tourmaline from Mashak Pahar, South Purulia Shear Zone (SPSZ), eastern Indian Shield - SANTANU ACHARJEE; JYOTISANKAR RAY; PAYEL DEY; DEBAPRIYA BHATTACHARYYA; MOUSUMI BANERJEE; BASAB CHATTOPADHYAY; SHYAMAL SENGUPTA; A K BHATT; D CHOWDHURY; A K DWIVEDI; SANJOY MAHATO; ARKA RANJAN JANA; et al. (Journal of Earth System Science, 2016)

A comprehensive insight on ocular pharmacokinetics - Vibhuti Agrahari; Abhirup Mandal; Vivek Agrahari; Hoang M. Trinh; Mary Joseph; Animikh Ray; Hicheme Hadji; Ranjana Mitra; Dhananjay Pal; Ashim K. Mitra (Drug Delivery and Translational Research, 2016)

Development and validation of cross-transferable and polymorphic DNA markers for detecting alien genome introgression in Oryza sativa from Oryza brachyantha - Soham Ray; Lotan K. Bose; Joshitha Ray; Umakanta Ngangkham; Jawahar L. Katara; Sanghamitra Samantaray; Lambodar Behera; Mahender Anumalla; Onkar N. Singh; Meingsheng Chen; Rod A. Wing; Trilochan Mohapatra (Molecular Genetics and Genomics, 2016)

Genome-wide association of familial prostate cancer cases identifies evidence for a rare segregating haplotype at 8q24.21 - Craig C. Teerlink; Daniel Leongamornlert; Tokhir Dadaev; Alun Thomas; James Farnham; Robert A. Stephenson; Shaun Riska; Shannon K. McDonnell; Daniel J. Schaid; William J. Catalona; S. Lilly Zheng; Kathleen A. Cooney; et al. (Human Genetics, 2016)

Neuron specific enolase: a promising therapeutic target in acute spinal cord injury - Azizul Haque; Swapan K. Ray; April Cox; Naren L. Banik (Metabolic Brain Disease, 2016)

Endophytic Alcaligenes Isolated from Horticultural and Medicinal Crops Promotes Growth in Okra (Abelmoschus esculentus) - Shatrupa Ray; Surendra Singh; B. K. Sarma; H. B. Singh (Journal of Plant Growth Regulation, 2016)

NSDF: Neuroscience Simulation Data Format - Subhasis Ray; Chaitanya Chintaluri; Upinder S. Bhalla; Daniel K. Wójcik (Neuroinformatics, 2016)

Identifying relevant group of miRNAs in cancer using fuzzy mutual information - Jayanta Kumar Pal; Shubhra Sankar Ray; Sankar K. Pal (Medical & Biological Engineering & Computing, 2016)

Morphotectonic and petrological variations along the southern Central Indian Ridge - Ranadhir Mukhopadhyay; Sridhar D. Iyer; Dwijesh Ray; S. M. Karisiddaiah; Rajendra K. Drolia (International Journal of Earth Sciences, 2016)

Kedarnath disaster 2013: causes and consequences using remote sensing inputs - P. K. Champati Ray; Shovan Lal Chattoraj; M. P. S. Bisht; Suresh Kannaujiya; Kamal Pandey; Ajanta Goswami (Natural Hazards, 2016)

Multi-view stereophotogrammetry for post-mastectomy breast reconstruction - Xiangyang Ju; Helga Henseler; Matthew Jian-qiao Peng; Balvinder S. Khambay; Arup K. Ray; Ashraf F. Ayoub (Medical & Biological Engineering & Computing, 2016)

Anti-tumor activities of luteolin and silibinin in glioblastoma cells: overexpression of miR-7-1-3p augmented luteolin and silibinin to inhibit autophagy and induce apoptosis in glioblastoma in vivo - Mrinmay Chakrabarti; Swapan K. Ray (Apoptosis, 2016)

Genistein ameliorates cardiac inflammation and oxidative stress in streptozotocin-induced diabetic cardiomyopathy in rats - Suresh K. Gupta; Shirish Dongare; Rajani Mathur; Ipseeta Ray Mohanty; Sushma Srivastava; Sandeep Mathur; Tapas C. Nag (Molecular and Cellular Biochemistry, 2015)

Science–policy processes for transboundary water governance - Derek Armitage; Rob C. de Loë; Michelle Morris; Tom W. D. Edwards; Andrea K. Gerlak; Roland I. Hall; Dave Huitema; Ray Ison; David Livingstone; Glen MacDonald; Naho Mirumachi; Ryan Plummer; et al. (Ambio, 2015)

Spatial prediction of landslide susceptibility in parts of Garhwal Himalaya, India, using the weight of evidence modelling - Pardeep Kumar Guri; P. K. Champati ray; Ramesh Chandra Patel (Environmental Monitoring and Assessment, 2015)

Tuberculosis surveillance of elephants (Elephas maximus) in Nepal at the captive-wild interface - Susan K. Mikota; Kamal Gairhe; Kamal Giri; Karin Hamilton; Michele Miller; Sarad Paudel; Konstantin Lyashchenko; R. Scott Larsen; Janet B. Payeur; W. Ray Waters; Rena Greenwald; Genevieve Dumonceaux; et al. (European Journal of Wildlife Research, 2015)

Development and Characterization of Sorbitan Monostearate and Sesame Oil-Based Organogels for Topical Delivery of Antimicrobials - Vinay K. Singh; Krishna Pramanik; Sirsendu S. Ray; Kunal Pal (AAPS PharmSciTech, 2015)

Erratum to: Genome-wide association study (GWAS) of carbon isotope ratio (δ13C) in diverse soybean [Glycine max (L.) Merr.] genotypes - Arun Prabhu Dhanapal; Jeffery D. Ray; Shardendu K. Singh; Valerio Hoyos-Villegas; James R. Smith; Larry C. Purcell; C. Andy King; Perry B. Cregan; Qijian Song; Felix B. Fritschi (Theoretical and Applied Genetics, 2015)

Genome-wide association study (GWAS) of carbon isotope ratio (δ13C) in diverse soybean [Glycine max (L.) Merr.] genotypes - Arun Prabhu Dhanapal; Jeffery D. Ray; Shardendu K. Singh; Valerio Hoyos-Villegas; James R. Smith; Larry C. Purcell; C. Andy King; Perry B. Cregan; Qijian Song; Felix B. Fritschi (Theoretical and Applied Genetics, 2015)

Assessing bee (Hymenoptera: Apoidea) diversity of an Illinois restored tallgrass prairie: methodology and conservation considerations - Ray K. Geroff; Jason Gibbs; Kenneth W. McCravy (Journal of Insect Conservation, 2014)

Microbial Biomass Carbon Status in Agro-Ecological Sub Regions of Black Soils in India - Kulandaivelu Velmourougane; M. V. Venugopalan; T. Bhattacharyya; Dipak Sarkar; D. K. Pal; Apeksha Sahu; P. Chandran; S. K. Ray; Champa Mandal; K. M. Nair; Jagdish Prasad; R. S. Singh; et al. (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Assessment of organochlorine pesticide residues in Indian flue-cured tobacco with gas chromatography-single quadrupole mass spectrometer - Rakesh Kumar Ghosh; Zareen S. Khan; C. V. N. Rao; Kaushik Banerjee; D. Damodar Reddy; T. G. K. Murthy; Nalli Johnson; Deb Prasad Ray (Environmental Monitoring and Assessment, 2014)

Quantitative Study of As (V) and As (III) Interaction with Mangrove DNA by Molecular Fluorescence Spectroscopy - N. Majumder; C. Chowdhury; R. Ray; T. K. Jana (Bulletin of Environmental Contamination and Toxicology, 2014)

Quantifying the dominance of local control and the sources of regional control in the assembly of a metacommunity - Chris Ray; Sharon K. Collinge (Ecology, 2014)
To understand the relative roles of local and regional processes in structuring local communities, and to compare sources of dispersal, we studied plant species composition in the context of a field experiment in vernal pool community assembly. In 1999, we constructed 256 vernal pools in a grid surrounding a group of over 60 naturally occurring reference pools. Each constructed pool received a seeding or control treatment. Seeding treatments involved several “focal species” native to vernal pools in this region. Earlier analyses identified local habitat quality (pool depth) and pool history (seeding treatment) as strong predictors of local species composition. For the current analysis, we asked how connectivity among pools might enhance models of focal species presence and cover within pools, using long‐term data from control pools and from unseeded transects within a stratified random sample of all constructed pools. We fitted connectivity models for each of four focal species, and compared the relative support for connectivity, seeding treatment, and pool depth as predictors of local species presence and cover. We modeled connectivity in several ways to quantify the relative importance of immigration (1) from constructed pools, (2) from reference pools within the study site, (3) from a cluster of natural pools off‐site, and (4) along ephemeral waterways. We found strongest support for effects of connectivity with reference pools. Species presence in a target pool was usually well predicted by an exponential decline in connectivity with distance to source pools, and our fitted estimates of mean dispersal distance indicate strong dispersal limitation in this system. Effects of target and source pool size were also supported in some models, and long‐term effects of seeding were supported for most species. However, pool depth was by far the strongest predictor of focal species presence, and depth rivaled connectivity with reference pools as a top predictor of cover after accounting for species presence. We conclude that local species composition was determined primarily by local processes in this system, and we encourage more widespread use of a straightforward method for weighing local vs. regional influences.

Possible Alteration of Female Specific Protein by Estradiol-17β in Silkworm, Bombyx mori L - Shantanu Das; Arun K. Ray (Proceedings of the Zoological Society, 2014)

Trends in seasonal temperatures over the Indian region - Nilesh K Wagholikar; K C Sinha Ray; P N Sen; P Pradeep Kumar (Journal of Earth System Science, 2014)

Developing Spectral Library of Major Plant Species of Western Himalayas Using Ground Observations - K. R. Manjunath; Amit Kumar; Mehra Meenakshi; R. Renu; S. K. Uniyal; R. D. Singh; P. S. Ahuja; S. S. Ray; Sushma Panigrahy (Journal of the Indian Society of Remote Sensing, 2014)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

Genetics and mapping of quantitative traits for nodule number, weight, and size in soybean (Glycine max L.[Merr.]) - Sadal Hwang; Jeffery D. Ray; Perry B. Cregan; C. Andy King; Marilynn K. Davies; Larry C. Purcell (Euphytica, 2014)

Urease Activity in Various Agro-ecological Sub-regions of Black Soil Regions of India - Kulandaivelu Velmourougane; M. V. Venugopalan; T. Bhattacharyya; Dipak Sarkar; D. K. Pal; Apeksha Sahu; P. Chandran; S. K. Ray; Champa Mandal; K. M. Nair; Jagdish Prasad; R. S. Singh; et al. (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2013)

Age and geochemistry of the Newania dolomite carbonatites, India: implications for the source of primary carbonatite magma - Jyotiranjan S. Ray; Kanchan Pande; Rajneesh Bhutani; Anil D. Shukla; Vinai K. Rai; Alok Kumar; Neeraj Awasthi; R. S. Smitha; Dipak K. Panda (Contributions to Mineralogy and Petrology, 2013)

Targeting oncogenic ALK and MET: a promising therapeutic strategy for glioblastoma - Gerald C. Wallace; Yaenette N. Dixon-Mah; W. Alex Vandergrift; Swapan K. Ray; Catherine P. Haar; Amber M. Mittendorf; Sunil J. Patel; Naren L. Banik; Pierre Giglio; Arabinda Das (Metabolic Brain Disease, 2013)

Sequential hTERT Knockdown and Apigenin Treatment Inhibited Invasion and Proliferation and Induced Apoptosis in Human Malignant Neuroblastoma SK-N-DZ and SK-N-BE2 Cells - Mrinmay Chakrabarti; Naren L. Banik; Swapan K. Ray (Journal of Molecular Neuroscience, 2013)

Dry season precipitation over the Mesoamerican Biological Corridor is more sensitive to deforestation than to greenhouse gas driven climate change - Deepak K. Ray (Climatic Change, 2013)

Impact of acamprosate on behavior and brain-derived neurotrophic factor: an open-label study in youth with fragile X syndrome - Craig A. Erickson; Logan K. Wink; Balmiki Ray; Maureen C. Early; Elizabeth Stiegelmeyer; Lauren Mathieu-Frasier; Vanessa Patrick; Debomoy K. Lahiri; Christopher J. McDougle (Psychopharmacology, 2013)

Evaluation of GPS orbit prediction strategies for the IGS Ultra-rapid products - Kevin K. Choi; Jim Ray; Jake Griffiths; Tae-Suk Bae (GPS Solutions, 2013)

SCS-CN Based Quantification of Potential of Rooftop Catchments and Computation of ASRC for Rainwater Harvesting - P. K. Singh; B. K. Yaduvanshi; Swati Patel; Saswati Ray (Water Resources Management, 2013)

Targeting RET to induce medullary thyroid cancer cell apoptosis: an antagonistic interplay between PI3K/Akt and p38MAPK/caspase-8 pathways - Minakshi Mazumdar; Arghya Adhikary; Samik Chakraborty; Shravanti Mukherjee; Argha Manna; Shilpi Saha; Suchismita Mohanty; Amrita Dutta; Pushpak Bhattacharjee; Pallab Ray; Sreya Chattopadhyay; Shuvomoy Banerjee; et al. (Apoptosis, 2013)

Historical thermal regimes define limits to coral acclimatization - Emily J. Howells; Ray Berkelmans; Madeleine J. H. van Oppen; Bette L. Willis; Line K. Bay (Ecology, 2013)
Knowledge of the degree to which corals undergo physiological acclimatization or genetic adaptation in response to changes in their thermal environment is crucial to the success of coral reef conservation strategies. The potential of corals to acclimatize to temperatures exceeding historical thermal regimes was investigated by reciprocal transplantation of Acropora millepora colonies between the warm central and cool southern regions of the Great Barrier Reef (GBR) for a duration of 14 months. Colony fragments retained at native sites remained healthy, whereas transplanted fragments, although healthy over initial months when temperatures remained within native thermal regimes, subsequently bleached and suffered mortality during seasonal temperature extremes. Corals hosting Symbiodinium D transplanted to the southern GBR bleached in winter and the majority suffered whole (40%; n = 20 colonies) or partial (50%) mortality at temperatures 1.1°C below their 15‐year native minimum. In contrast, corals hosting Symbiodinium C2 transplanted to the central GBR bleached in summer and suffered whole (50%; n = 10 colonies) or partial (42%) mortality at temperatures 2.5°C above their 15‐year native maximum. During summer bleaching, the dominant Symbiodinium type changed from C2 to D within corals transplanted to the central GBR. Corals transplanted to the cooler, southern GBR grew 74–80% slower than corals at their native site, and only 50% of surviving colonies reproduced, at least partially because of cold water bleaching of transplants. Despite the absence of any visual signs of stress, corals transplanted to the warmer, central GBR grew 52–59% more slowly than corals at their native site before the summer bleaching (i.e., from autumn to spring). Allocation of energy to initial acclimatization or reproduction may explain this pattern, as the majority (65%) of transplants reproduced one month earlier than portions of the same colonies retained at the southern native site. All parameters investigated (bleaching, mortality, Symbiodinium type fidelity, reproductive timing) demonstrated strong interactions between genotype and environment, indicating that the acclimatization potential of A. millepora populations may be limited by adaptation of the holobiont to native thermal regimes.

Implication of Organic Matter on Arsenic and Antimony Sequestration in Sediment: Evidence from Sundarban Mangrove Forest, India - S. K. Mandal; R. Ray; C. Chowdhury; N. Majumder; T. K. Jana (Bulletin of Environmental Contamination and Toxicology, 2013)

Agricultural Area Diversification and Crop Water Demand Analysis: A Remote Sensing and GIS Approach - B. U. Choudhury; Anil Sood; S. S. Ray; P. K. Sharma; S. Panigrahy (Journal of the Indian Society of Remote Sensing, 2013)

Genome size variation among sex types in dioecious and trioecious Caricaceae species - Andrea R. Gschwend; Ching Man Wai; Francis Zee; Aru K. Arumuganathan; Ray Ming (Euphytica, 2013)

The muscarinic M1 receptor positive allosteric modulator PQCA improves cognitive measures in rat, cynomolgus macaque, and rhesus macaque - Jason M. Uslaner; Donnie Eddins; Vanita Puri; Christopher E. Cannon; Jane Sutcliffe; Chan Sing Chew; Michelle Pearson; Jeffrey A. Vivian; Ronald K. Chang; William J. Ray; Scott D. Kuduk; Marion Wittmann (Psychopharmacology, 2013)

Novel 4H-1,2,4-triazol-3-yl cycloalkanols as potent antitubercular agents - Nutan H. Palsule Desai; Ranjeet Bairwa; Manoj Kakwani; Nilesh Tawari; M. K. Ray; M. G. Rajan; Mariam Degani (Medicinal Chemistry Research, 2013)

Mitigating future climate change effects by shifting planting dates of crops in rice–wheat cropping system - S. K. Jalota; Harsimran Kaur; S. S. Ray; R. Tripathi; Bharat Bhushan Vashisht; S. K. Bal (Regional Environmental Change, 2012)

Acaricide resistance status in Indian isolates of Hyalomma anatolicum - K. P. Shyma; Sachin Kumar; Anil Kumar Sharma; D. D. Ray; S. Ghosh (Experimental and Applied Acarology, 2012)

Phosphorus Solubilization by Thermotolerant Bacillus subtilis Isolated from Cow Dung Microflora - Manas R. Swain; K. Laxminarayana; Ramesh C. Ray (Agricultural Research, 2012)

Crop Residue Discrimination Using Ground-Based Hyperspectral Data - Rimjhim Bhatnagar Singh; S. S. Ray; S. K. Bal; B. S. Sekhon; G. S. Gill; Sushma Panigrahy (Journal of the Indian Society of Remote Sensing, 2012)

Sedimentological and 14C dating studies of past tsunami events in Southern Sri Lanka - Kapila Dahanayake; Nayomi Kulasena; G. V. Ravi Prasad; Koushik Dutta; D. K. Ray (Natural Hazards, 2012)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Optimization of Culture Conditions for Production of Protease by Two Bacterial Strains, Bacillus licheniformis BF2 and Bacillus subtilis BH4 Isolated from the Digestive Tract of Bata, Labeo bata (Hamilton) - A. K. Ray; S. Mondal; T. Roy (Proceedings of the Zoological Society, 2012)

Genome size variation in three Saccharum species - Jisen Zhang; Chifumi Nagai; Qingyi Yu; Yong-Bao Pan; Tomas Ayala-Silva; Raymond J. Schnell; Jack C. Comstock; Aru K. Arumuganathan; Ray Ming (Euphytica, 2012)

Effects of roof and rainwater characteristics on copper concentrations in roof runoff - Gretchen K. Bielmyer; W. Ray Arnold; Joseph R. Tomasso; Jeff J. Isely; Stephen J. Klaine (Environmental Monitoring and Assessment, 2012)

Connectivity of prairie dog colonies in an altered landscape: inferences from analysis of microsatellite DNA variation - Loren C. Sackett; Todd B. Cross; Ryan T. Jones; Whitney C. Johnson; Kimberly Ballare; Chris Ray; Sharon K. Collinge; Andrew P. Martin (Conservation Genetics, 2012)

Analysis of transcriptional and upstream regulatory sequence activity of two environmental stress-inducible genes, NBS-Str1 and BLEC-Str8, of rice - Swatismita Ray; Sanjay Kapoor; Akhilesh K. Tyagi (Transgenic Research, 2012)

Rice Blast Management Through Host-Plant Resistance: Retrospect and Prospects - T. R. Sharma; A. K. Rai; S. K. Gupta; J. Vijayan; B. N. Devanna; S. Ray (Agricultural Research, 2012)

Soluplus-Solubilized Citrated Camptothecin—A Potential Drug Delivery Strategy in Colon Cancer - Naveen K. Thakral; Alok R. Ray; Daniel Bar-Shalom; André Huss Eriksson; Dipak K. Majumdar (AAPS PharmSciTech, 2012)

Native polyubiquitin promoter of rice provides increased constitutive expression in stable transgenic rice plants - Jagannath Bhattacharyya; Asif Hasan Chowdhury; Samarjit Ray; Jyoti Krishna Jha; Srirupa Das; Srimonta Gayen; Anirban Chakraborty; Joy Mitra; Mrinal K. Maiti; Asitava Basu; Soumitra K. Sen (Plant Cell Reports, 2012)

Movement and persistence by Ross’s Geese (Chen rossii) in Canada’s arctic - Ray T. Alisauskas; Kiel L. Drake; Jason H. Caswell; Dana K. Kellett (Journal of Ornithology, 2012)

Comparing the benefits of screening for breast cancer and lung cancer using a novel natural history model - Ray S. Lin; Sylvia K. Plevritis (Cancer Causes & Control, 2012)

Longli is not a Hybrid of Longan and Lychee as Revealed by Genome Size Analysis and Trichome Morphology - Robert VanBuren; Jianguo Li; Francis Zee; Jianhua Zhu; Chengming Liu; Aru K. Arumuganathan; Ray Ming (Tropical Plant Biology, 2011)

Discrimination of Spectrally-Close Crops Using Ground-Based Hyperspectral Data - K. R. Manjunath; Shibendu Shankar Ray; Sushma Panigrahy (Journal of the Indian Society of Remote Sensing, 2011)

Introduction to Special Issue of Bulletin of Volcanology on “Advances in Kimberlite Geology and Volcanology” - Ray Cas; J. K. Russell; R. Stephen J. Sparks (Bulletin of Volcanology, 2011)

A Spatial Database of Cropping System and its Characteristics to Aid Climate Change Impact Assessment Studies - Sushma Panigrahy; Shibendu Shankar Ray; K. R. Manjunath; P. S. Pandey; S. K. Sharma; Anil Sood; Manoj Yadav; P. C. Gupta; N. Kundu; Jai Singh Parihar (Journal of the Indian Society of Remote Sensing, 2011)

Phytoplankton abundance in relation to cultural eutrophication at the land-ocean boundary of Sunderbans, NE Coast of Bay of Bengal, India - Tarun Kumar De; Minati De; Subhajit Das; Chumki Chowdhury; Raghab Ray; Tapan K. Jana (Journal of Environmental Studies and Sciences, 2011)

VEGF-C differentially regulates VEGF-A expression in ocular and cancer cells; promotes angiogenesis via RhoA mediated pathway - Bharat Kumar; Shailaja A. Chile; Kriti B. Ray; G. E. C. Vidyadhar Reddy; Murali K. Addepalli; A. S. Manoj Kumar; Venkata Ramana; Vikram Rajagopal (Angiogenesis, 2011)

Utility of Hyperspectral Data for Potato Late Blight Disease Detection - Shibendu Shankar Ray; Namrata Jain; R. K. Arora; S. Chavan; Sushma Panigrahy (Journal of the Indian Society of Remote Sensing, 2011)

Glucosinolate content and nematicidal activity of Brazilian wild mustard tissues against Meloidogyne incognita in tomato - Rosângela D. L. Oliveira; Onkar D. Dhingra; André O. Lima; Gulab N. Jham; Mark A. Berhow; Ray K. Holloway; Steven F. Vaughn (Plant and Soil, 2011)

Modulation of transcription factor and metabolic pathway genes in response to water-deficit stress in rice - Swatismita Ray; Prasant K. Dansana; Jitender Giri; Priyanka Deveshwar; Rita Arora; Pinky Agarwal; Jitendra P. Khurana; Sanjay Kapoor; Akhilesh K. Tyagi (Functional & Integrative Genomics, 2011)

A regional scale assessment of land use/land cover and climatic changes on water and energy cycle in the upper Midwest United States - Vimal Mishra; Keith A. Cherkauer; Dev Niyogi; Ming Lei; Bryan C. Pijanowski; Deepak K. Ray; Laura C. Bowling; Guoxiang Yang (International Journal of Climatology, 2010)
This study examines the relative impact of regional land‐cover/land‐use patterns and projected future climate change on hydrologic processes. Historic, present and projected future land cover data were used to drive the variable infiltration capacity (VIC) model using observed meteorological forcing data for 1983–2007 over Wisconsin (USA). The current and projected future (year 2030) land cover data were developed using the land transformation model (LTM). The VIC model simulations were driven using downscaled and bias‐corrected projected future climate forcing from three different Intergovernmental Panel for Climate Change (IPCC) AR4 general circulation models (GCMs): HadCM3, PCM and GFDL. Sensitivity results conducted on a single grid cell show that annual average surface runoff and baseflow were increased by 8 and 6 mm, respectively, while evapotranspiration was reduced by 15 mm when a fully forested grid was converted to cropland. Results also indicate that annual average net radiation and sensible heat flux were reduced considerably due to forest‐to‐cropland conversion, and the reduction was more prominent in winter and spring seasons due to effect of snow albedo. Forest‐to‐cropland conversion also resulted in increased latent heat flux in summer (JJA) while this land transformation increased the snow water equivalent in winter (DJF) and spring (MAM). Complete conversion of forest to cropland resulted in a decrease of the radiative surface temperature on an annual basis with more cooling occurring in winter and summer. Impacts of historic deforestation were similar to what was expected based on a single grid sensitivity analysis. Copyright © 2010 Royal Meteorological Society

Evaluating the protection of wildlife in parks: the case of African buffalo in Serengeti - K. L. Metzger; A. R. E. Sinclair; Ray Hilborn; J. Grant C. Hopcraft; Simon A. R. Mduma (Biodiversity and Conservation, 2010)

Level of Heavy Metals in Some Edible Marine Fishes of Mangrove Dominated Tropical Estuarine Areas of Hooghly River, North East Coast of Bay of Bengal, India - T. K. De; M. De; S. Das; R. Ray; P. B. Ghosh (Bulletin of Environmental Contamination and Toxicology, 2010)

Feasibility Evaluation of Pressurized Irrigation in Canal Commands - Ramesh C. Srivastava; Sheelabhadra Mohanty; Ramlal B. Singandhuppe; Rajiv K. Mohanty; Madhu S. Behera; Lala I. P. Ray; Deepika Sahoo (Water Resources Management, 2010)

Peptides representing the specific variable regions but not the full porin proteins can be useful for antibody based diagnosis of typhoid fever - S. Kumar; S. Kapil; V. Gautam; S. K. Verma; P. Ray (Folia Microbiologica, 2010)

The Impact of Future Land Use Scenarios on Runoff Volumes in the Muskegon River Watershed - Deepak K. Ray; Jonah M. Duckles; Bryan C. Pijanowski (Environmental Management, 2010)

Are functional deficits in concussed individuals consistent with white matter structural alterations: combined FMRI & DTI study - K. Zhang; B. Johnson; D. Pennell; W. Ray; W. Sebastianelli; S. Slobounov (Experimental Brain Research, 2010)

Shift in detrital sedimentation in the eastern Bay of Bengal during the late Quaternary - C. Prakash Babu; J. N. Pattan; K. Dutta; N. Basavaiah; G. V. Ravi Prasad; D. K. Ray; P. Govil (Journal of Earth System Science, 2010)

Functional abnormalities in normally appearing athletes following mild traumatic brain injury: a functional MRI study - Semyon M. Slobounov; K. Zhang; D. Pennell; W. Ray; B. Johnson; W. Sebastianelli (Experimental Brain Research, 2010)

Evaluation of plasma hormone concentrations using Enzyme-Immunoassay/Enzyme-linked Immunosorbent assay in healthy Indian men: Effect of ethnicity - M. Sachidhanandam; S. N. Singh; A. K. Salhan; Uday Sankar Ray (Indian Journal of Clinical Biochemistry, 2010)

Carbon and oxygen isotopic compositions of Newania Dolomite Carbonatites, Rajasthan, India: implications for source of carbonatites - Jyotiranjan S. Ray; Anil D. Shukla; Lokesh K. Dewangan (Mineralogy and Petrology, 2010)

Antioxidant and oxidative stress responses of sojourners at high altitude in different climatic temperatures - Sanchari Sinha; Som Nath Singh; Mantu Saha; T. C. Kain; A. K. Tyagi; Uday Sankar Ray (International Journal of Biometeorology, 2010)

Hydrologic and biotic influences on nitrate removal in a subtropical spring‐fed river - James B. Heffernan; Matthew J. Cohen; Thomas K. Frazer; Ray G. Thomas; Travis J. Rayfield; Jason Gulley; Jonathan B. Martin; Joseph J. Delfino; Wendy D. Graham (Limnology and Oceanography, 2010)
We use a long‐term chemical and hydrologic record in combination with longitudinal sampling and high‐frequency nitrate (NO 3 ‐ ) measurements from in situ sensors to describe temporal and spatial patterns of nitrogen (N) inputs and removal in the spring‐fed Ichetucknee River (Columbia County, Florida) and to determine the hydrological, geomorphic, and biological factors that influence those dynamics. Over a 20‐yr period of record, NO 3 ‐N removal averaged 118 kg N d ‐1 (0.77 g N m ‐2 d ‐1 ) over the upper 5 km of the Ichetucknee River. Three independent estimates of gross autotrophicNassimilation (from gross primary production, diel NO 3 ‐ variation, and standing biomass) agreed closely but accounted for less than 20% of observed N removal. Longitudinal surveys indicate negligible or negative dissolved organic nitrogen and ammonium (NH 4 + ) production, suggesting that denitrification is the predominant mechanism of N removal in this river. A positive relationship between discharge and the magnitude of NO 3 ‐N removal shows that interactions with the surrounding floodplain exert considerable influence at high flows, and longitudinal NO 3 ‐ patterns indicate that N removal may be influenced by channel morphology. These results suggest a greater role for dissimilatory processes and hydrologic connectivity with hyporheic and floodplain sediments than has been previously recognized in highly productive spring‐fed rivers of north Florida. While hydrologic variation is the primary determinant of variation in NO 3 ‐ removal within the Ichetucknee River, comparison across systems indicates that biotic characteristics can cause significant deviation from predictions based on purely physical models of relationships between river size and N removal.

Transient patterns in the assembly of vernal pool plant communities - Sharon K. Collinge; Chris Ray (Ecology, 2009)
Community assembly theory asserts that the contemporary composition of ecological communities may depend critically on events that occur during the formation of the community; a phenomenon termed “historical contingence.” We tested key aspects of this theory using plant communities in over 200 experimentally created vernal pools at a field site in central California, USA. The experiment was initiated in 1999 with construction of vernal pool basins into which different seeding treatments were imposed to evaluate the effects of dispersal limitation, order of colonization (“priority effects”), and frequency of colonization on plant community composition. We tracked the abundance and distribution of five focal species for seven years following seeding and observed strong but transient effects of seeding, as well as order and frequency of colonization. All five species occurred with higher frequency in seeded pools vs. unseeded control pools, demonstrating dispersal limitation. Three of four species exerted strong priority effects, with much higher abundance in pools in which they were seeded first compared to pools in which they were seeded in the second year of the study, one year after other species were seeded. We tested for effects of frequency of colonization using one species, the endangered Lasthenia conjugens , and observed much higher abundance in frequently vs. infrequently seeded pools for the first four years following seeding. Finally, we observed that the strength of priority effects varied significantly with water depth for one of the species groups, which demonstrates that abiotic context can strongly influence species interactions. We conclude that several aspects of historical contingence play key roles in the early formation of vernal pool plant communities. But we also observed reversals in community trajectories, suggesting that in this system historical effects may be lost within a decade.

IRS-LISS-III and PAN data analysis for landslide susceptibility mapping using heuristic approach in active tectonic region of Himalaya - M. A. A. Patwary; P. K. Champati ray; Irshad Parvaiz (Journal of the Indian Society of Remote Sensing, 2009)

Impact of cropping pattern changes on the exploitation of water resources: A remote sensing and GIS approach - Anil Sood; B. U. Choudhury; S. S. Ray; S. K. Jalota; P. K. Sharma; Shushma Panigrahy (Journal of the Indian Society of Remote Sensing, 2009)

Microcapsules and Transdermal Patch: A Comparative Approach for Improved Delivery of Antidiabetic Drug - Manoj K. Mishra; Debajyoti Ray; Bhakti B. Barik (AAPS PharmSciTech, 2009)

Study on the utility of IRS-P6 AWiFS SWIR band for crop discrimination and classification - Rabindra K. Panigrahy; S. S. Ray; S. Panigrahy (Journal of the Indian Society of Remote Sensing, 2009)

Improvement in predictability of waves over the Indian Ocean - Raj Kumar; Suchandra A. Bhowmick; Sulagna Ray; Vihang Bhatt; Suhe Surendran; Sujit Basu; Abhijit Sarkar; Vijay K. Agarwal (Natural Hazards, 2009)

Evaluation of test results of microbiology laboratories of North India for standard tests for syphilis under an external quality assurance scheme - S. M. Gupta; M. Bala; S. Muralidhar; K. Ray (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Leaf isoprene emission rate as a function of atmospheric CO 2 concentration - MICHAEL J. WILKINSON; RUSSELL K. MONSON; NICOLE TRAHAN; STANFIELD LEE; ERIN BROWN; ROBERT B. JACKSON; H. WAYNE POLLEY; PHILIP A. FAY; RAY FALL (Global Change Biology, 2009)
There is considerable interest in modeling isoprene emissions from terrestrial vegetation, because these emissions exert a principal control over the oxidative capacity of the troposphere. We used a unique field experiment that employs a continuous gradient in CO 2 concentration from 240 to 520 ppmv to demonstrate that isoprene emissions in Eucalyptus globulus were enhanced at the lowest CO 2 concentration, which was similar to the estimated CO 2 concentrations during the last Glacial Maximum, compared with 380 ppmv, the current CO 2 concentration. Leaves of Liquidambar styraciflua did not show an increase in isoprene emission at the lowest CO 2 concentration. However, isoprene emission rates from both species were lower for trees grown at 520 ppmv CO 2 compared with trees grown at 380 ppmv CO 2 . When grown in environmentally controlled chambers, trees of Populus deltoides and Populus tremuloides exhibited a 30–40% reduction in isoprene emission rate when grown at 800 ppmv CO 2 , compared with 400 ppmv CO 2 . P. tremuloides exhibited a 33% reduction when grown at 1200 ppmv CO 2 , compared with 600 ppmv CO 2 . We used current models of leaf isoprene emission to demonstrate that significant errors occur if the CO 2 inhibition of isoprene is not taken into account. In order to alleviate these errors, we present a new model of isoprene emission that describes its response to changes in atmospheric CO 2 concentration. The model logic is based on assumed competition between cytosolic and chloroplastic processes for pyruvate, one of the principal substrates of isoprene biosynthesis.

Latent structure of facets of alcohol reinforcement from a behavioral economic demand curve - James MacKillop; James G. Murphy; Jennifer W. Tidey; Christopher W. Kahler; Lara A. Ray; Warren K. Bickel (Psychopharmacology, 2009)

Fruit Development, Ripening and Quality Related Genes in the Papaya Genome - Robert E. Paull; Beth Irikura; Pingfang Wu; Helen Turano; Nancy Jung Chen; Andrea Blas; John K. Fellman; Andrea R. Gschwend; Ching Man Wai; Qingyi Yu; Gernot Presting; Maqsudul Alam; et al. (Tropical Plant Biology, 2008)

Complex genetics of glaucoma: defects in CYP1B1, and not MYOC, cause pathogenesis in an early-onset POAG patient with double variants at both loci - Moulinath Acharya; Arijit Mukhopadhyay; Ashima Bhattacharjee; Sanjay K. D. Thakur; Arun K. Bandyopadhyay; Kunal Ray (Journal of Genetics, 2008)

Trace Element Concentrations in Blood of Nesting King Eiders in the Canadian Arctic - Mark Wayland; Ray T. Alisauskas; Dana K. Kellett; Katherine R. Mehl (Archives of Environmental Contamination and Toxicology, 2008)

Influence of neotectonic activity on groundwater salinity and playa development in the Mendha river catchment, western India - V. S. Rathore; M. S. Nathawat; P. K. Champati Ray (International Journal of Remote Sensing, 2008)

Production and characterization of extracellular protease of mutant Aspergillus niger AB100 grown on fish scale - Barnali Ray Basu; Ajit K. Banik; Manas Das (World Journal of Microbiology and Biotechnology, 2008)

Pharmacodynamic and pharmacokinetic characterisation of RBx 7796: a novel 5-lipoxygenase inhibitor - R. K. Shirumalla; P. Sharma; S. G. Dastidar; J. K. Paliwal; S. Kakar; B. Varshney; G. Singh Saini; V. Sattigeri; M. Salman; A. Ray (Inflammation Research, 2008)

Expression analysis of calcium-dependent protein kinase gene family during reproductive development and abiotic stress conditions in rice (Oryza sativa L. ssp. indica) - Swatismita Ray; Pinky Agarwal; Rita Arora; Sanjay Kapoor; Akhilesh K. Tyagi (Molecular Genetics and Genomics, 2007)

Genome-wide identification of C2H2 zinc-finger gene family in rice and their phylogeny and expression analysis - Pinky Agarwal; Rita Arora; Swatismita Ray; Ashok K. Singh; Vijay P. Singh; Hiroshi Takatsuji; Sanjay Kapoor; Akhilesh K. Tyagi (Plant Molecular Biology, 2007)

Seismic microzonation of Dehradun City using geophysical and geotechnical characteristics in the upper 30 m of soil column - A. K. Mahajan; Siefko Slob; Rajiv Ranjan; Rob Sporry; P. K. Champati ray; Cees J. van Westen (Journal of Seismology, 2007)

Combination of all-trans retinoic acid and taxol regressed glioblastoma T98G xenografts in nude mice - Surajit Karmakar; Naren L. Banik; Sunil J. Patel; Swapan K. Ray (Apoptosis, 2007)

Gene ordering in partitive clustering using microarray expressions - Shubhra Sankar Ray; Sanghamitra Bandyopadhyay; Sankar K. Pal (Journal of Biosciences, 2007)

Fuzzy-based method for landslide hazard assessment in active seismic zone of Himalaya - P. K. Champati ray; Suvarna Dimri; R. C. Lakhera; Santosh Sati (Landslides, 2007)

Garlic compounds induced calpain and intrinsic caspase cascade for apoptosis in human malignant neuroblastoma SH-SY5Y cells - Surajit Karmakar; Naren L. Banik; Sunil J. Patel; Swapan K. Ray (Apoptosis, 2007)

Polymerase Chain Reaction (PCR) Amplification of IS6110 Sequences to detect Mycobacterium tuberculosis Complex from Formalin-fixed Paraffin-embedded Tissues of Deer (Axis axis) - S. Sharma; G. P. Mallick; Rishendra Verma; S. K. Ray (Veterinary Research Communications, 2007)

Mapping of fault rupture of the 28 may 2004 iran earthquake (mw= 6.2) using satellite image - M. Sharifikia; C. S. Dubey; B. K. Sharma; M. Chaudhry; P. K. Champati Ray (Journal of the Indian Society of Remote Sensing, 2006)

RBx 7796: A novel inhibitor of 5-lipoxygenase - R. K. Shirumalla; K. S. Naruganahalli; S. G. Dastidar; V. Sattigeri; G. Kaur; C. Deb; J. B. Gupta; M. Salman; A. Ray (Inflammation Research, 2006)

Association of OPRM1 A118G variant with the relative reinforcing value of nicotine - R. Ray; C. Jepson; F. Patterson; A. Strasser; M. Rukstalis; K. Perkins; K. G. Lynch; S. O’Malley; W. H. Berrettini; C. Lerman (Psychopharmacology, 2006)

Genetic characterization of VP3 gene of group A rotaviruses - Swati Subodh; Maharaj K Bhan; Pratima Ray (Virus Genes, 2006)

Light-regulated overexpression of an Arabidopsis phytochrome A gene in rice alters plant architecture and increases grain yield - Ajay K. Garg; Ruairidh J. H. Sawers; Haiyang Wang; Ju-Kon Kim; Joseph M. Walker; Thomas P. Brutnell; Mandayam V. Parthasarathy; Richard D. Vierstra; Ray J. Wu (Planta, 2006)

Reproductive history, occupational exposures, and thyroid cancer risk among women textile workers in Shanghai, China - E. Y. Wong; R. Ray; D. L. Gao; K. J. Wernli; W. Li; E. D. Fitzgibbons; Z. Feng; D. B. Thomas; H. Checkoway (International Archives of Occupational and Environmental Health, 2006)

Letter to the Editor - Basant K. Tiwary; R. Kirubagaran; Arun K. Ray (Reviews in Fish Biology and Fisheries, 2006)

A Quick appraisal of ground deformation in indian region due to the october 8, 2005 earthquake, Muzaffarabad, Pakistan - P. K. Champati ray; R. J. G. Perumal; V. C. Thakur; M. I. Bhat; M. A. Mallik; Vivek Kumar Singh; R. C. Lakhera (Journal of the Indian Society of Remote Sensing, 2005)

Colorectal Cancer Incidence Among Female Textile Workers in Shanghai, China: A Case-cohort Analysis of Occupational Exposures - A.J. De Roos; R. M. Ray; D. L. Gao; K. J. Wernli; E. D. Fitzgibbons; F. Ziding; G. Astrakianakis; D. B. Thomas; H. Checkoway (Cancer Causes & Control, 2005)

Molecular pathogenesis of Wilson disease: haplotype analysis, detection of prevalent mutations and genotype–phenotype correlation in Indian patients - A. Gupta; D. Aikath; R. Neogi; S. Datta; K. Basu; B. Maity; R. Trivedi; J. Ray; S. K. Das; P. K. Gangopadhyay; K. Ray (Human Genetics, 2005)

Least cost SO2 emission minimization for a petroleum refinery by optimum use of source reduction, tail gas treatment and flue gas desulphurization - A. K. Dikshit; Amit Dutta; S. Ray (Clean Technologies and Environmental Policy, 2005)

Molecular basis of protective effect by crocetin on survival and liver tissue damage following hemorrhagic shock - Animesh Dhar; George Cherian; Gopal Dhar; Gibanananda Ray; Ram Sharma; Sushanta K. Banerjee (Molecular and Cellular Biochemistry, 2005)

Accuracy assessment of InSAR derived input maps for landslide susceptibility analysis: a case study from the Swiss Alps - Lalan P. Singh; C. J. van Westen; P. K. Champati Ray; P. Pasquali (Landslides, 2005)

An expressed sequence tag SSR map of tetraploid alfalfa (Medicago sativa L.) - M. K. Sledge; I. M. Ray; G. Jiang (Theoretical and Applied Genetics, 2005)

Evolutionary innovation: a bone‐eating marine symbiosis - Shana K. Goffredi; Victoria J. Orphan; Greg W. Rouse; Linda Jahnke; Tsegeria Embaye; Kendra Turk; Ray Lee; Robert C. Vrijenhoek (Environmental Microbiology, 2005)
Summary Symbiotic associations between microbes and invertebrates have resulted in some of the most unusual physiological and morphological adaptations that have evolved in the animal world. We document a new symbiosis between marine polychaetes of the genus Osedax and members of the bacterial group Oceanospirillales, known for heterotrophic degradation of complex organic compounds. These organisms were discovered living on the carcass of a grey whale at 2891 m depth in Monterey Canyon, off the coast of California. The mouthless and gutless worms are unique in their morphological specializations used to obtain nutrition from decomposing mammalian bones. Adult worms possess elaborate posterior root‐like extensions that invade whale bone and contain bacteriocytes that house intracellular symbionts. Stable isotopes and fatty acid analyses suggest that these unusual endosymbionts are likely responsible for the nutrition of this locally abundant and reproductively prolific deep‐sea worm.

Fishing Rights or Fishing Wrongs? - Ray Hilborn; Julia K. Parrish; Kate Litle (Reviews in Fish Biology and Fisheries, 2005)

Use of GIS and remote sensing for crop diversification — a case study for Punjab state - S. S. Ray; Anil Sood; Gargi Das; Sushma Panigrahy; P. K. Sharma; J. S. Parihar (Journal of the Indian Society of Remote Sensing, 2005)

Water quality assessment of Gautami — Godavari mangrove estuarine ecosystem of Andhra Pradesh, India during September 2001 - S. C. Tripathy; A. K. Ray; S. Patra; V. V. Sarma (Journal of Earth System Science, 2005)

The biology of triploid fish - Basant K. Tiwary; R. Kirubagaran; Arun K. Ray (Reviews in Fish Biology and Fisheries, 2004)

Analysis of cropping pattern changes in Bathinda district, Punjab - Sushma Panigrahy; S. S. Ray; Anil Sood; L. B. Patel; P. K. Sharma; J. S. Parihar (Journal of the Indian Society of Remote Sensing, 2004)

Alterations in air‐sac and skeleton of triploid Heteropneustes fossilis - B. K. Tiwary; A. K. Ray (Journal of Fish Biology, 2004)
Triploid stinging catfish Heteropneustes fossilis, when produced by cold shock, showed abnormalities in their air‐sacs and skeletons.

Removal process estimation of population size for a population with a known sex ratio - Liping Liu; Paul S.F. Yip; Ray K. Watson (Environmental and Ecological Statistics, 2003)

DDT and HCH Residues in Basmati Rice (Oryza sativa) Cultivated in Dehradun (India) - G. Suresh Babu; M. Farooq; R. S. Ray; P. C. Joshi; P. N. Viswanathan; R. K. Hans (Water, Air, & Soil Pollution, 2003)

A facile reactor process for producing 7,10-dihydroxy-8(E)-octadecenoic acid from oleic acid conversion by Pseudomonas aeruginosa ** - Tsung Min Kuo; Karen J. Ray; Linda K. Manthey (Biotechnology Letters, 2003)

Antioxidant activity of ethanol extract of rhizome ofPicrorhiza kurroa on indomethacin induced gastric ulcer during healing - Arun Ray; Susri Ray Chaudhuri; Biswajit Majumdar; Sandip K. Bandyopadhyay (Indian Journal of Clinical Biochemistry, 2002)

Environmental impact assessment and its minimisation in a refinery using life cycle impact analysis approach - Amit Dutta; A. K. Dikshit; S. Ray; M. Bandyopadhyay (The International Journal of Life Cycle Assessment, 2002)

Strategies for carbon acquisition in the red marine macroalga Coccotylus truncatus from the Baltic Sea - Snoeijs P.; Klenell M.; Choo K.; Comhaire I.; Ray S.; Pedersén M. (Marine Biology, 2002)

Protein A-activated macrophages induce apoptosis in Ehrlich's ascites carcinoma through a nitric oxide-dependent pathway - S. Chattopadhyay; T. Das; G. Sa; P. K. Ray (Apoptosis, 2002)

Potent antiulcerogenic activity of ethanol extract of leaf ofPiper betle Linn by antioxidative mechanism - Biswajit Majumdar; Susri Ray Chaudhuri; Arun Ray; Sandip K Bandyopadhyay (Indian Journal of Clinical Biochemistry, 2002)

Temperature Sensitivity of Timing Measurements Using Dorne Margolin Antennas - J. R. Ray; K. Senior (GPS Solutions, 2001)

Identification and classification of aromatic rices based on DNA fingerprinting - P. Ray Choudhury; S. Kohli; K. Srinivasan; T. Mohapatra; R.P. Sharma (Euphytica, 2001)

Tobacco and Arabidiopsis SLT1 mediate salt tolerance of yeast - Tracie K. Matsumoto; Jose M. Pardo; Satomi Takeda; Ray A. Bressan; Paul M. Hasegawa (Plant Molecular Biology, 2001)

Integrated commodity management methods with ca and/or fumigation - S. Prabhakaran; S. Ray; B. M. Schneider; R. E. Williams; P. Flinn; T. Phillips; D. Hagstrum; F. Arthur; J. Throne; R. N. Emery; R. A. Tassone; E. Kostas; et al. (Phytoparasitica, 2001)

Plasma levels of Gonadotropin-II and gonadal sex steroids in triploid catfish, Heteropneustes fossilis (Bloch) - Basant K. Tiwary; R. Kirubagaran; Arun K. Ray (Fish Physiology and Biochemistry, 2001)

Serum lipids, lipoproteins and sex-hormone binding globulin in breast cancer - A. Ray; S. L. Dayalu Naik; A. K. Bahadur; S. T. Pasha; R. S. Rautela; B. K. Sharma (Indian Journal of Clinical Biochemistry, 2001)

Status of epidermal growth factor receptors family in hormone-dependent carcinomas of the breast and prostate with reference to serum lipids and lipoproteins - D. Jain; A. Ray; A. K. Bahadur; K. U. Chaturvedi; R. Sood; S. Sharma; S. L. D. Naik; B. K. Sharma (Indian Journal of Clinical Biochemistry, 2001)

Land Use/Land Cover Change Mapping In Mahi Canal Command Area, Gujarat, Using Multi-temporal Satellite Data - V. S. Brahmabhatt; G. B. Dalwadi; S. B. Chhabra; S. S. Ray; V. K. Dadhwal (Journal of the Indian Society of Remote Sensing, 2000)

Protection of apoptotic cell death by protein A - Prasanta K. Ray; Tanya Das; Gaurisankar Sa; Amiya K. Ghosh; Sreya Chattopadhyay (Apoptosis, 2000)

Gonadal development in triploid Heteropneustes fossilis - B. K. Tiwary; R. Kirubagaran; A. K. Ray (Journal of Fish Biology, 2000)
Gonadosomatic index ( I G ) and germ cell numbers in seminiferous tubules were significantly reduced in triploid male catfish compared with diploids. Triploid females had lower I G than diploids, with atretic follicles in their ovaries during prespawning and spawning phases.

Role of light in the mediation of acute effects of a single afternoon melatonin injection on steroidogenic activity of testis in the rat - Saumen K. Maitra; Arun K. Ray (Journal of Biosciences, 2000)

A rare case of two malignancies: Carcinoma of the breast and uterine cervix - A. Ray; H. Mukundan; A. K. Bahadur; R. S. Rautela; S. L. D. Naik; B. K. Sharma (Indian Journal of Clinical Biochemistry, 2000)

Breast and prostate cancer - B. K. Sharma; A. Ray (Indian Journal of Clinical Biochemistry, 2000)

Antifungal activity of venenatine, an indole alkaloid isolated fromAlstonia venenata - U. P. Singh; B. K. Sarma; P. K. Mishra; A. B. Ray (Folia Microbiologica, 2000)

Physico-Chemical Quality of Drinking Water in Rohtas District of Bihar - D. Ray; R. Ravindar Rao; A. V. Bhoi; A. K. Biswas; A. K. Ganguly; P. B. Sanyal (Environmental Monitoring and Assessment, 2000)

Partitioning linear trends in age-adjusted rates - Benjamin F. Hankey; Lynn A. Ries; Carol L. Kosary; Eric J. Feuer; Ray M. Merrill; Limin X. Clegg; Brenda K. Edwards (Cancer Causes & Control, 2000)

The modified wave estimator as an alternative to a Kalman filter for real-time GPS/GLONASS-INS integration - J. K. Ray; O. S. Salychev; M. E. Cannon (Journal of Geodesy, 1999)

Antifungal activity of Δ3-alstovenine, a plant alkaloid isolated fromAlstonia venenata - S. K. Singh; B. K. Sarma; J. S. Srivastava; U. P. Singh; A. B. Ray (Folia Microbiologica, 1999)

Reactive oxygen species function as second messenger during ischemic preconditioning of heart - Dipak K. Das; Nilanjana Maulik; Motoaki Sato; Partha S. Ray (Molecular and Cellular Biochemistry, 1999)

Stress genes and species survival - Prasanta K. Ray (Molecular and Cellular Biochemistry, 1999)

The significance of synoptic patterns identified by the Kirchhofer technique: A Monte Carlo approach - Robert K. Kaufmann; Seth E. Snell; Sucharita Gopal; Ray Dezzani (International Journal of Climatology, 1999)

The significance of synoptic patterns identified by the Kirchhofer technique: A Monte Carlo approach - Robert K. Kaufmann; Seth E. Snell; Sucharita Gopal; Ray Dezzani (International Journal of Climatology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Adaptation to low temperature and regulation of gene expression in antarctic psychrotrophic bacteria - Malay K Ray; G Seshu Kumar; Kamala Janiyani; K Kannan; Pratik Jagtap; Malay K Basu; S Shivaji (Journal of Biosciences, 1998)

Differential alterations in metabolic pattern of the six major UsnRNAs during development - Rabindranath Ray; Kaushik Ray; Chinmay K. Panda (Molecular and Cellular Biochemistry, 1997)

Studies on mercury-detoxicating enzymes from a broad-spectrum mercury-resistant strain ofFlavobacterium rigense - R. Gachhui; J. Chaudhuri; S. Ray; K. Pahan; A. Mandal (Folia Microbiologica, 1997)

Tissue-specific activation of the osmotin gene by ABA, C2H4 and NaCl involves the same promoter region - K. G. Raghothama; Albino Maggio; Meena L. Narasimhan; Andrzej K. Kononowicz; Guangli Wang; Matilde Paino D'Urzo; Paul M. Hasegawa; Ray A. Bressan (Plant Molecular Biology, 1997)

Transgenic sorghum plants obtained after microprojectile bombardment of immature inflorescences - Ana M. Casas; Andrzej K. Kononowicz; Theresa G. Haan; Lanying Zhang; Dwight T. Tomes; Ray A. Bressan; Paul M. Hasegawa (In Vitro Cellular & Developmental Biology - Plant, 1997)

Effect of methyl isocyanate (MIC) on rat erythrocytes - Deepa Agrawal; G. S. D. Gupta; J. S. Shukla; K. K. Dutta; P. K. Ray (Archives of Toxicology, 1990)

A study of nerve conduction velocity, late responses and neuromuscular synapse functions in organophosphate workers in India - U. K. Misra; D. Nag; W. A. Khan; P. K. Ray (Archives of Toxicology, 1988)

Occurrence of cyclic adenosine 3?,5?-monophosphate in the phytopathogenic fungi Alternaria solani and Phymatotrichum omnivorum - Radheshyam K. Jayaswal; Ray A. Bressan; Avtar K. Handa (Archives of Microbiology, 1983)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)